Glass ceramic with spinel crystal phase and glass ceramic product
By adjusting the component ratio of the crystal crystal glass and the Li2O/TiO2 ratio, the glass coloring problem caused by Ti3+ ions is solved, and a microcrystalline glass with excellent light transmittance and mechanical properties is achieved.
Patent Information
- Application Number
- CN202510269173.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-27
- Publication Date
- 2025-05-09
AI Technical Summary
Preparation of microcrystalline glasses with spinel phases in the prior art can easily lead to the presence of Ti3+ ions, resulting in the coloration of the glass and reduce the transmittance.
By adjusting the component ratio, the Li2O2/TiO2 ratio is contained in the range of 0.2 to 4.5 to 45%, Li2O2:0.1 to 6%, MgO:0.1 to 6%, TiO2:0.5 to 7%, and the Li2O/TiO2 ratio is controlled to reduce the formation of Ti3+.
A microcrystalline glass with spinel crystal phase with excellent light transmittance and mechanical properties has been realized, which has improved its application potential in electronic devices and display devices.
Smart Images

Figure BDA0005302150800000291 
Figure BDA0005302150800000321 
Figure BDA0005302150800000331
Abstract
Description
[0001] This application is a divisional application for the invention patent application with application number 202310470742.X, application date April 27, 2023, and name “Microcrystalline glass and microcrystalline glass products with spinel crystal phase”. Technical Field
[0002] The invention relates to a glass-ceramic, in particular to a glass-ceramic having a spinel crystal phase and a glass-ceramic product. Background Art
[0003] Glass-ceramics is a polycrystalline solid material formed by the controlled crystallization of glass with specific components. It has the structural characteristics and properties of both glass and ceramics. It is a new type of inorganic non-metallic material that is being developed and has broad application prospects. Glass-ceramics has excellent properties such as high mechanical strength, low thermal expansion coefficient, good corrosion resistance, high hardness and good wear resistance. It can be used in electronics, machinery, aerospace, biomedicine and other fields.
[0004] Glass-ceramics with spinel crystal phases are used in display devices or electronic devices, especially in the front and back covers of portable electronic devices (such as mobile phones, watches, PADs, etc.). Compared with materials such as ceramics and sapphire, they have obvious advantages. Glass-ceramics with spinel crystal phases have a smooth surface, a completely dense and uniform structure, are not easy to stain, and have a relatively simple process, large production capacity, and low cost. Compared with high-aluminum glass, glass-ceramics with spinel crystal phases have higher mechanical strength, hardness, drop resistance, thermal conductivity, and better thermal stability and chemical stability.
[0005] In the prior art, TiO2 is used as a nucleating agent to prepare spinel crystal glass. However, the Ti element introduced by TiO2 is prone to change in valence in the glass to form Ti 3+ Ion. Ti 3+ Ions tend to exist stably in the formed crystalline phase, causing the glass-ceramics to be colored (brown-yellow), thereby reducing the transmittance of the glass-ceramics in the visible light region. In addition, the refractive index of spinel is relatively high (1.83), which is quite different from the refractive index of the matrix glass. The precipitation of the spinel crystal phase will also reduce the transmittance of the glass-ceramics in the visible light region. The above factors restrict the application of glass-ceramics with spinel crystal phase in electronic devices and display devices. Therefore, how to improve the transmittance of glass-ceramics with spinel crystal phase is also an urgent problem to be solved. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a glass-ceramic having a spinel crystal phase and a glass-ceramic product having excellent light transmittance and mechanical properties.
[0007] The technical solution adopted by the present invention to solve the technical problem is:
[0008] (1) Glass-ceramic products with a spinel crystal phase, whose components, expressed in weight percentage, contain: SiO2: 40-55%; Al2O3+ZnO: 26-45%; Li2O: 0.1-6%; MgO: 0.1-6%; TiO2: 0.5-7%, wherein Li2O / TiO2 is 0.2-4.5.
[0009] (2) The microcrystalline glass product having a spinel crystal phase according to (1), wherein the components, expressed in weight percentage, further contain: P2O5+ZrO2: 0-8%; and / or Na2O: 0-6%; and / or B2O3: 0-4%; and / or K2O: 0-3%; and / or CaO+BaO+SrO: 0-5%; and / or Y2O3: 0-6%; and / or clarifier: 0-2%.
[0010] (3) Glass-ceramic products with a spinel crystal phase, whose components include SiO2, Al2O3, Li2O, ZnO and TiO2, and the light transmittance of the glass-ceramic products with a thickness of less than 1 mm at a wavelength of 550 nm is more than 87.0%.
[0011] (4) A glass-ceramic product having a spinel crystal phase, wherein the components thereof include SiO2, Al2O3, Li2O, ZnO and TiO2, and wherein the drop resistance of the glass-ceramic product is above 1200 mm.
[0012] (5) A glass-ceramic product having a spinel crystal phase, wherein the components thereof include SiO2, Al2O3, and ZnO, and wherein the compressive strength of the glass-ceramic product is greater than 400N.
[0013] (6) Glass-ceramic products having a spinel crystal phase, the haze of the glass-ceramic products having a thickness of less than 1 mm is less than 0.3%.
[0014] (7) A glass-ceramic product having a spinel crystal phase, wherein the drop ball test height of the glass-ceramic product is greater than 1000 mm.
[0015] (8) Glass-ceramic products with a spinel crystal phase, whose components include SiO2, Al2O3, Li2O, ZnO and TiO2, and the average optical |B| value of 400 to 800nm of the glass-ceramic products with a thickness of less than 1mm is less than 1.0.
[0016] (9) A glass-ceramic product having a spinel crystal phase, wherein the components thereof include SiO2, Al2O3, Li2O, ZnO and TiO2, wherein the depth of the ion exchange layer of the glass-ceramic product is greater than 75 μm.
[0017] (10) A glass-ceramic product having a spinel crystal phase, wherein the components thereof include SiO2, Al2O3, and Li2O, and wherein the surface stress of the glass-ceramic product is greater than 200 MPa.
[0018] (11) A glass-ceramic product having a spinel crystal phase, wherein the components thereof include SiO2, Al2O3, ZnO and TiO2, and wherein the grain size of the glass-ceramic product is less than 60 nm.
[0019] (12) Glass-ceramics products having a spinel crystal phase, wherein the light transmittance of the glass-ceramics products having a thickness of less than 1 mm at a wavelength of 550 nm is greater than 87.0%.
[0020] (13) A glass-ceramic product having a spinel crystal phase, wherein the components thereof include SiO2, Al2O3 and ZnO, and wherein the Vickers hardness of the glass-ceramic product is 650 kgf / mm 2 above.
[0021] (14) A glass-ceramic product having a spinel crystal phase according to any one of (3) to (13), wherein the components, expressed in weight percentage, are: SiO2: 40 to 55%; and / or Al2O3+ZnO: 26 to 45%; and / or Li2O: 0.1 to 6%; and / or MgO: 0.1 to 6%; and / or TiO2: 0.5 to 7%; and / or P2O5+ZrO2: 0 to 8%; and / or Na2O: 0 to 6%; and / or B2O3: 0 to 4%; and / or K2O: 0 to 3%; and / or CaO+BaO+SrO: 0 to 5%; and / or Y2O3: 0 to 6%; and / or a clarifier: 0 to 2%.
[0022] (15) A glass-ceramic product having a spinel crystal phase, the components of which, expressed in weight percentage, are SiO2: 40-55%; Al2O3+ZnO: 26-45%; Li2O: 0.1-6%; MgO: 0.1-6%; TiO2: 0.5-7%; P2O5+ZrO2: 0-8%; Na2O: 0-6%; B2O3: 0-4%; K2O: 0-3%; CaO+BaO+SrO: 0-5%; Y2O3: 0-6%; and a clarifier: 0-2%.
[0023] (16) A glass-ceramic product having a spinel crystal phase according to any one of (1) to (15), wherein the components are expressed in weight percentage, wherein: Li2O / TiO2 is 0.2 to 4.5, preferably Li2O / TiO2 is 0.5 to 3.5, more preferably Li2O / TiO2 is 0.7 to 2.5, and further preferably Li2O / TiO2 is 0.75 to 1.5.
[0024] (17). A glass-ceramic product having a spinel crystal phase according to any one of (1) to (15), wherein the components are expressed in weight percentage, wherein: Al2O3 / ZnO is 1.0 to 3.0, preferably Al2O3 / ZnO is 1.2 to 2.8, more preferably Al2O3 / ZnO is 1.25 to 2.5, and further preferably Al2O3 / ZnO is 1.5 to 2.3.
[0025] (18). A glass-ceramic product having a spinel crystal phase according to any one of (1) to (15), wherein the components are expressed in weight percentage, wherein: SiO2 / Al2O3 is 1.5 to 3.2, preferably SiO2 / Al2O3 is 1.7 to 3.0, more preferably SiO2 / Al2O3 is 1.8 to 2.8, and further preferably SiO2 / Al2O3 is 2.0 to 2.5.
[0026] (19). A glass-ceramic product having a spinel crystal phase according to any one of (1) to (15), wherein the components are expressed in weight percentage, wherein: (TiO2+ZnO) / Al2O3 is 0.4 to 1.5, preferably (TiO2+ZnO) / Al2O3 is 0.5 to 1.2, more preferably (TiO2+ZnO) / Al2O3 is 0.6 to 1.0, and further preferably (TiO2+ZnO) / Al2O3 is 0.6 to 0.9.
[0027] (20). A glass-ceramic product having a spinel crystal phase according to any one of (1) to (15), wherein the components are expressed in weight percentage, wherein: (Li2O+MgO) / TiO2 is 0.3 to 8.0, preferably (Li2O+MgO) / TiO2 is 0.5 to 5.0, more preferably (Li2O+MgO) / TiO2 is 1.0 to 3.0, and further preferably (Li2O+MgO) / TiO2 is 1.2 to 2.5.
[0028] (21). A glass-ceramic product having a spinel crystal phase according to any one of (1) to (15), wherein the components are expressed in weight percentage, wherein: Al2O3 / (MgO+TiO2) is 1.3 to 10.0, preferably Al2O3 / (MgO+TiO2) is 1.5 to 8.0, more preferably Al2O3 / (MgO+TiO2) is 2.5 to 6.5, and further preferably Al2O3 / (MgO+TiO2) is 3.0 to 5.5.
[0029] (22). A glass-ceramic product having a spinel crystal phase according to any one of (1) to (15), wherein the components are expressed in weight percentage, wherein: (Al2O3+Li2O) / P2O5 is 5.0 to 45.0, preferably (Al2O3+Li2O) / P2O5 is 7.0 to 35.0, more preferably (Al2O3+Li2O) / P2O5 is 8.0 to 30.0, and further preferably (Al2O3+Li2O) / P2O5 is 10.0 to 25.0.
[0030] (23). A glass-ceramic product having a spinel crystal phase according to any one of (1) to (15), wherein the components are expressed in weight percentage, wherein: P2O5 / ZrO2 is 0.1 to 5.0, preferably P2O5 / ZrO2 is 0.2 to 3.0, more preferably P2O5 / ZrO2 is 0.5 to 2.0, and further preferably P2O5 / ZrO2 is 0.6 to 1.5.
[0031] (24). A glass-ceramic product having a spinel crystal phase according to any one of (1) to (15), wherein the components are expressed in weight percentage, wherein: (SiO2+Na2O) / ZnO is 2.2 to 6.2, preferably (SiO2+Na2O) / ZnO is 2.5 to 6.0, more preferably (SiO2+Na2O) / ZnO is 2.8 to 5.5, and further preferably (SiO2+Na2O) / ZnO is 3.0 to 5.0.
[0032] (25). A glass-ceramic product having a spinel crystal phase according to any one of (1) to (15), wherein the components are expressed in weight percentage, wherein: (Na2O+K2O) / ZnO is less than 0.8, preferably (Na2O+K2O) / ZnO is less than 0.6, more preferably (Na2O+K2O) / ZnO is less than 0.4, and further preferably (Na2O+K2O) / ZnO is less than 0.2.
[0033] (26) A glass-ceramic product having a spinel crystal phase according to any one of (1) to (15), wherein the components, expressed in weight percentage, comprise: SiO2: 45-53%, preferably SiO2: 48-52%; and / or Al2O3+ZnO: 30-42%, preferably Al2O3+ZnO: 32-42%, more preferably Al2O3+ZnO: 35-40%; and / or Li2O: 1-5%, preferably Li2O: 2-4%; and / or MgO: 1-5%, preferably MgO: 2-4%; and / or TiO2: 1-6%, preferably TiO2: 2 ~5%; and / or P2O5+ZrO2: 0.1~7%, preferably P2O5+ZrO2: 0.5~5%; and / or Na2O: 0~4%, preferably Na2O: 0~2%; and / or B2O3: 0~2%, preferably B2O3: 0~1%; and / or K2O: 0~2%, preferably K2O: 0~1%; and / or CaO+BaO+SrO: 0~4%, preferably CaO+BaO+SrO: 0~2%; and / or Y2O3: 0~4%, preferably Y2O3: 0~2%; and / or clarifier: 0~1%, preferably clarifier: 0~0.5%.
[0034] (27). A glass-ceramic product having a spinel crystal phase according to any one of (1) to (15), wherein the components, expressed in weight percentage, contain: Al2O3: 15 to 30%, preferably Al2O3: 18 to 25%, more preferably Al2O3: 20 to 23%; and / or ZnO: 9 to 20%, preferably ZnO: 11 to 18%, more preferably ZnO: 12 to 16%; and / or P2O5: 0 to 5%, preferably P2O5: 0.5 to 4%, more preferably P2O5: 1 to 3%; and / or ZrO2: 0 to 5%, preferably ZrO2: 0.5 to 4%, more preferably ZrO2: 1 to 3%.
[0035] (28). According to any one of (1) to (15) of the microcrystalline glass product having a spinel crystal phase, the weight percentage of the spinel crystal phase in the microcrystalline glass product is 20 to 60%, preferably the weight percentage of the spinel crystal phase in the microcrystalline glass product is 25 to 50%, more preferably the weight percentage of the spinel crystal phase in the microcrystalline glass product is 25 to 45%, and further preferably the weight percentage of the spinel crystal phase in the microcrystalline glass product is 30 to 45%.
[0036] (29). A glass-ceramic product having a spinel crystal phase according to any one of (1) to (15), wherein the glass-ceramic product having a spinel crystal phase contains a quartz crystal phase, and preferably the weight percentage of the quartz crystal phase in the glass-ceramic product is less than 20%, more preferably the weight percentage of the quartz crystal phase in the glass-ceramic product is less than 10%, further preferably the weight percentage of the quartz crystal phase in the glass-ceramic product is less than 5%, and further preferably the glass-ceramic product having a spinel crystal phase does not contain a quartz crystal phase.
[0037] (30) A glass-ceramic product having a spinel crystal phase according to any one of (1) to (14), wherein the components, expressed in weight percentage, contain: La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-5%, preferably La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-2 %, more preferably La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0~1%, further preferably contains no La2O3, and / or no Gd2O3, and / or no Yb2O3, and / or no Nb2O5, and / or no WO3, and / or no Bi2O3, and / or no Ta2O5, and / or no TeO2.
[0038] (31) A glass-ceramic product having a spinel crystal phase according to any one of (1) to (15), wherein the grain size of the glass-ceramic product is 60 nm or less, preferably 45 nm or less, and more preferably 10 to 30 nm; and / or the depth of the ion exchange layer is 75 μm or more, preferably 80 to 150 μm, and more preferably 100 to 125 μm; and / or the surface stress is 200 MPa or more, preferably 250 to 400 MPa, and more preferably 300 to 400 MPa; and / or the height of the drop ball test is 1000 mm or more, preferably 1200 mm or more, and more preferably 1500 mm or more; and / or the drop resistance is 1200 mm or more, preferably 1300 mm or more, and more preferably 1400 mm or more; and / or the fracture toughness is 1.0 MPa·m 1 / 2 Above, preferably 1.2 MPa·m 1 / 2 More preferably, 1.2 to 1.6 MPa·m 1 / 2 ; and / or a four-point bending strength of 500 MPa or more, preferably 600 MPa or more, more preferably 700-1000 MPa; and / or an extrusion strength of 400 N or more, preferably 400-550 N, more preferably 450-550 N; and / or a Vickers hardness of 650 kgf / mm 2 Above, preferably 660kgf / mm2 More preferably, 680 to 750 kgf / mm 2 .
[0039] (32). According to any one of (1) to (15) of the microcrystalline glass product having a spinel crystal phase, the haze of the microcrystalline glass product with a thickness of less than 1 mm is less than 0.3%, preferably less than 0.25%, and more preferably 0.05-0.2%; and / or the average light transmittance at a wavelength of 400-800 nm is greater than 87.0%, preferably greater than 88.5%, and more preferably greater than 89.5%; and / or the light transmittance at a wavelength of 550 nm is greater than 87.0%, preferably greater than 88.0%, and more preferably greater than 89.0%; and / or the average light |B| value at 400-800 nm is less than 1.0, preferably less than 0.8, and more preferably 0.3-0.6.
[0040] (33) The microcrystalline glass product having a spinel crystal phase according to (32), wherein the thickness of the microcrystalline glass product is 0.2 to 1 mm, preferably 0.3 to 0.9 mm, more preferably 0.5 to 0.8 mm, and further preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm or 0.75 mm.
[0041] (34) A glass-ceramic product having a spinel crystal phase according to any one of (1) to (14), wherein the components, expressed in weight percentage, include: NiO: 0-4%; and / or Ni2O3: 0-4%; and / or CoO: 0-2%; and / or Co2O3: 0-2%; and / or Fe2O3: 0-7%; and / or MnO2: 0-4%; and / or Er2O3: 0-8%; and / or Nd2O3: 0-8%; and / or Cu2O: 0-4%; and / or Pr2O3: 0-8%; and / or CeO2: 0-4%.
[0042] (35) A glass-ceramic product having a spinel crystal phase according to any one of (1) to (14), wherein the components, expressed in weight percentage, include: NiO: 0.1-4%; and / or Ni2O3: 0.1-4%; and / or CoO: 0.05-2%; and / or Co2O3: 0.05-2%; and / or Fe2O3: 0.2-7%; and / or MnO2: 0.1-4%; and / or Er2O3: 0.4-8%; and / or Nd2O3: 0.4-8%; and / or Cu2O: 0.5-4%; and / or Pr2O3: 0.4-8%; and / or CeO2: 0.5-4%.
[0043] (36) A glass-ceramic product having a spinel crystal phase according to any one of (1) to (14), wherein the components, expressed in weight percentage, include: NiO: 0.1-3%; and / or Ni2O3: 0.1-3%; and / or CoO: 0.05-1.8%; and / or Co2O3: 0.05-1.8%; and / or Fe2O3: 0.2-5%; and / or MnO2: 0.1-3%; and / or Er2O3: 0.4-6%; and / or Nd2O3: 0.4-6%; and / or Cu2O: 0.5-3%; and / or Pr2O3: 0.4-6%; and / or CeO2: 0.5-3%.
[0044] (37) A glass-ceramic product having a spinel crystal phase according to any one of (1) to (14), wherein the components thereof, expressed in weight percentage, contain: NiO: 0.1 to 3%; and / or Ni2O3: 0.1 to 3%.
[0045] (38) A glass-ceramic product having a spinel crystal phase according to any one of (1) to (14), wherein the components thereof, expressed in weight percentage, contain: CoO: 0.05 to 1.8%; and / or Co2O3: 0.05 to 1.8%.
[0046] (39) A glass-ceramic product having a spinel crystal phase according to any one of (1) to (14), wherein the components thereof, expressed in weight percentage, contain: Cu2O: 0.5 to 3%; and / or CeO2: 0.5 to 3%.
[0047] (40). A glass-ceramic product having a spinel crystal phase according to any one of (1) to (14), wherein the components, expressed in weight percentage, are: Fe2O3: 0.2-5%, CoO: 0.05-0.3%; or Fe2O3: 0.2-5%, Co2O3: 0.05-0.3%; or Fe2O3: 0.2-5%, CoO: 0.05-0.3%, NiO: 0.1-1%; or Fe2O3: 0.2-5%, Co2O3: 0.05-0.3%, NiO: 0.1-1%.
[0048] (41). A glass-ceramic product having a spinel crystal phase according to any one of (1) to (14), wherein the components, expressed in weight percentage, contain: Pr2O3: 0.4 to 6%; or Fe2O3: 0.2 to 5%; or MnO2: 0.1 to 3%; or Er2O3: 0.4 to 6%; or Nd2O3: 0.4 to 6%.
[0049] (42) A glass-ceramic product having a spinel crystal phase according to any one of (1) to (14), wherein the components thereof, expressed in weight percentage, comprise: Er2O3: 0.4 to 6%, Nd2O3: 0.4 to 4%, and MnO2: 0.1 to 2%.
[0050] (43) Glass-ceramics having a spinel crystal phase, the components of which, expressed in weight percentage, include: SiO2: 40-55%; Al2O3+ZnO: 26-45%; Li2O: 0.1-6%; MgO: 0.1-6%; TiO2: 0.5-7%, wherein the ratio of Li2O / TiO2 is 0.2-4.5.
[0051] (44). The microcrystalline glass having a spinel crystal phase according to (43), wherein its components, expressed in weight percentage, further contain: P2O5+ZrO2: 0-8%; and / or Na2O: 0-6%; and / or B2O3: 0-4%; and / or K2O: 0-3%; and / or CaO+BaO+SrO: 0-5%; and / or Y2O3: 0-6%; and / or clarifier: 0-2%.
[0052] (45) Glass-ceramics with a spinel crystal phase, whose components include SiO2, Al2O3, Li2O, ZnO and TiO2, and the light transmittance of the glass-ceramics with a thickness of less than 1 mm at a wavelength of 550 nm is more than 87.0%.
[0053] (46) Glass-ceramics having a spinel crystal phase, wherein the grain size of the glass-ceramics is less than 60 nm.
[0054] (47) Glass-ceramics having a spinel crystal phase, the components of which include SiO2, Al2O3, Li2O, ZnO and TiO2, and the haze of the glass-ceramics having a thickness of less than 1 mm is less than 0.3%.
[0055] (48) Glass-ceramics having a spinel crystal phase, the components of which include SiO2, Al2O3, ZnO and TiO2, and the Young's modulus of the glass-ceramics is 80 to 110 GPa.
[0056] (49) Glass-ceramics having a spinel crystal phase, wherein the components thereof include SiO2, Al2O3, Li2O and ZnO, wherein the average optical |B| value at 400 to 800 nm of the glass-ceramics having a thickness of less than 1 mm is less than 1.0.
[0057] (50) Glass-ceramics with a spinel crystal phase, whose components include SiO2, Al2O3 and ZnO, and the average light transmittance of the glass-ceramics with a thickness of less than 1 mm at a wavelength of 400 to 800 nm is more than 87.0%.
[0058] (51) The glass-ceramics having a spinel crystal phase according to any one of (45) to (50), wherein the components, expressed in weight percentage, are: SiO2: 40 to 55%; and / or Al2O3+ZnO: 26 to 45%; and / or Li2O: 0.1 to 6%; and / or MgO: 0.1 to 6%; and / or TiO2: 0.5 to 7%; and / or P2O5+ZrO2: 0 to 8%; and / or Na2O: 0 to 6%; and / or B2O3: 0 to 4%; and / or K2O: 0 to 3%; and / or CaO+BaO+SrO: 0 to 5%; and / or Y2O3: 0 to 6%; and / or clarifier: 0 to 2%.
[0059] (52) Glass-ceramics having a spinel crystal phase, whose components, expressed in weight percentage, are SiO2: 40-55%; Al2O3+ZnO: 26-45%; Li2O: 0.1-6%; MgO: 0.1-6%; TiO2: 0.5-7%; P2O5+ZrO2: 0-8%; Na2O: 0-6%; B2O3: 0-4%; K2O: 0-3%; CaO+BaO+SrO: 0-5%; Y2O3: 0-6%; and clarifier: 0-2%.
[0060] (53). The microcrystalline glass having a spinel crystal phase according to any one of (43) to (52), wherein the components are expressed in weight percentage, wherein: Li2O / TiO2 is 0.2 to 4.5, preferably Li2O / TiO2 is 0.5 to 3.5, more preferably Li2O / TiO2 is 0.7 to 2.5, and further preferably Li2O / TiO2 is 0.75 to 1.5.
[0061] (54). The glass-ceramics having a spinel crystal phase according to any one of (43) to (52), wherein the components are expressed in weight percentage, wherein: Al2O3 / ZnO is 1.0 to 3.0, preferably Al2O3 / ZnO is 1.2 to 2.8, more preferably Al2O3 / ZnO is 1.25 to 2.5, and further preferably Al2O3 / ZnO is 1.5 to 2.3.
[0062] (55). The glass-ceramics having a spinel crystal phase according to any one of (43) to (52), wherein the components are expressed in weight percentage, wherein: SiO2 / Al2O3 is 1.5 to 3.2, preferably SiO2 / Al2O3 is 1.7 to 3.0, more preferably SiO2 / Al2O3 is 1.8 to 2.8, and further preferably SiO2 / Al2O3 is 2.0 to 2.5.
[0063] (56). The microcrystalline glass having a spinel crystal phase according to any one of (43) to (52), wherein the components are expressed in weight percentage, wherein: (TiO2+ZnO) / Al2O3 is 0.4 to 1.5, preferably (TiO2+ZnO) / Al2O3 is 0.5 to 1.2, more preferably (TiO2+ZnO) / Al2O3 is 0.6 to 1.0, and further preferably (TiO2+ZnO) / Al2O3 is 0.6 to 0.9.
[0064] (57). The microcrystalline glass having a spinel crystal phase according to any one of (43) to (52), wherein the components are expressed in weight percentage, wherein: (Li2O+MgO) / TiO2 is 0.3 to 8.0, preferably (Li2O+MgO) / TiO2 is 0.5 to 5.0, more preferably (Li2O+MgO) / TiO2 is 1.0 to 3.0, and further preferably (Li2O+MgO) / TiO2 is 1.2 to 2.5.
[0065] (58). The microcrystalline glass having a spinel crystal phase according to any one of (43) to (52), wherein the components are expressed in weight percentage, wherein: Al2O3 / (MgO+TiO2) is 1.3 to 10.0, preferably Al2O3 / (MgO+TiO2) is 1.5 to 8.0, more preferably Al2O3 / (MgO+TiO2) is 2.5 to 6.5, and further preferably Al2O3 / (MgO+TiO2) is 3.0 to 5.5.
[0066] (59). A glass-ceramic having a spinel crystal phase according to any one of (43) to (52), wherein the components are expressed in weight percentage, wherein: (Al2O3+Li2O) / P2O5 is 5.0 to 45.0, preferably (Al2O3+Li2O) / P2O5 is 7.0 to 35.0, more preferably (Al2O3+Li2O) / P2O5 is 8.0 to 30.0, and further preferably (Al2O3+Li2O) / P2O5 is 10.0 to 25.0.
[0067] (60). The microcrystalline glass having a spinel crystal phase according to any one of (43) to (52), wherein the components are expressed in weight percentage, wherein: P2O5 / ZrO2 is 0.1 to 5.0, preferably P2O5 / ZrO2 is 0.2 to 3.0, more preferably P2O5 / ZrO2 is 0.5 to 2.0, and further preferably P2O5 / ZrO2 is 0.6 to 1.5.
[0068] (61). The glass-ceramics having a spinel crystal phase according to any one of (43) to (52), wherein the components are expressed in weight percentage, wherein: (SiO2+Na2O) / ZnO is 2.2 to 6.2, preferably (SiO2+Na2O) / ZnO is 2.5 to 6.0, more preferably (SiO2+Na2O) / ZnO is 2.8 to 5.5, and further preferably (SiO2+Na2O) / ZnO is 3.0 to 5.0.
[0069] (62). The glass-ceramics having a spinel crystal phase according to any one of (43) to (52), wherein the components are expressed in weight percentage, wherein: (Na2O+K2O) / ZnO is less than 0.8, preferably (Na2O+K2O) / ZnO is less than 0.6, more preferably (Na2O+K2O) / ZnO is less than 0.4, and further preferably (Na2O+K2O) / ZnO is less than 0.2.
[0070] (63) The glass-ceramics having a spinel crystal phase according to any one of (43) to (52), wherein the components, expressed in weight percentage, are: SiO2: 45-53%, preferably SiO2: 48-52%; and / or Al2O3+ZnO: 30-42%, preferably Al2O3+ZnO: 32-42%, more preferably Al2O3+ZnO: 35-40%; and / or Li2O: 1-5%, preferably Li2O: 2-4%; and / or MgO: 1-5%, preferably MgO: 2-4%; and / or TiO2: 1-6%, preferably TiO2: 2-6%. 5%; and / or P2O5+ZrO2: 0.1~7%, preferably P2O5+ZrO2: 0.5~5%; and / or Na2O: 0~4%, preferably Na2O: 0~2%; and / or B2O3: 0~2%, preferably B2O3: 0~1%; and / or K2O: 0~2%, preferably K2O: 0~1%; and / or CaO+BaO+SrO: 0~4%, preferably CaO+BaO+SrO: 0~2%; and / or Y2O3: 0~4%, preferably Y2O3: 0~2%; and / or clarifier: 0~1%, preferably clarifier: 0~0.5%.
[0071] (64). The microcrystalline glass having a spinel crystal phase according to any one of (43) to (52), wherein the components, expressed in weight percentage, contain: Al2O3: 15 to 30%, preferably Al2O3: 18 to 25%, more preferably Al2O3: 20 to 23%; and / or ZnO: 9 to 20%, preferably ZnO: 11 to 18%, more preferably ZnO: 12 to 16%; and / or P2O5: 0 to 5%, preferably P2O5: 0.5 to 4%, more preferably P2O5: 1 to 3%; and / or ZrO2: 0 to 5%, preferably ZrO2: 0.5 to 4%, more preferably ZrO2: 1 to 3%.
[0072] (65). According to any one of (43) to (52) of the microcrystalline glass having a spinel crystal phase, the weight percentage of the spinel crystal phase in the microcrystalline glass is 20 to 60%, preferably the weight percentage of the spinel crystal phase in the microcrystalline glass is 25 to 50%, more preferably the weight percentage of the spinel crystal phase in the microcrystalline glass is 25 to 45%, and further preferably the weight percentage of the spinel crystal phase in the microcrystalline glass is 30 to 45%.
[0073] (66). The glass-ceramic having a spinel crystal phase according to any one of (43) to (52), wherein the glass-ceramic having a spinel crystal phase contains a quartz crystal phase, and preferably the weight percentage of the quartz crystal phase in the glass-ceramic is less than 20%, more preferably the weight percentage of the quartz crystal phase in the glass-ceramic is less than 10%, further preferably the weight percentage of the quartz crystal phase in the glass-ceramic is less than 5%, and further preferably the glass-ceramic having a spinel crystal phase does not contain a quartz crystal phase.
[0074] (67) The glass-ceramics having a spinel crystal phase according to any one of (43) to (51), wherein the components, expressed in weight percentage, contain: La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-5%, preferably La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-2 %, more preferably La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0~1%, further preferably contains no La2O3, and / or no Gd2O3, and / or no Yb2O3, and / or no Nb2O5, and / or no WO3, and / or no Bi2O3, and / or no Ta2O5, and / or no TeO2.
[0075] (68) A glass-ceramic having a spinel crystal phase according to any one of (43) to (52), wherein the glass-ceramic has a grain size of 60 nm or less, preferably 45 nm or less, and more preferably 10 to 30 nm; and / or a Young's modulus of 80 to 110 GPa, preferably 85 to 105 GPa, and more preferably 90 to 105 GPa; and / or a Vickers hardness of 550 kgf / mm 2 Above, preferably 580kgf / mm 2 More preferably, 600 to 650 kgf / mm 2 .
[0076] (69). According to any one of (43) to (52) of the microcrystalline glass having a spinel crystal phase, the haze of the microcrystalline glass with a thickness of less than 1 mm is less than 0.3%, preferably less than 0.25%, and more preferably 0.05 to 0.2%; and / or the average light transmittance at a wavelength of 400 to 800 nm is greater than 87.0%, preferably greater than 88.5%, and more preferably greater than 89.5%; and / or the light transmittance at a wavelength of 550 nm is greater than 87.0%, preferably greater than 88.0%, and more preferably greater than 89.0%; and / or the average light |B| value at 400 to 800 nm is less than 1.0, preferably less than 0.8, and more preferably 0.3 to 0.6.
[0077] (70) According to the microcrystalline glass having a spinel crystal phase as described in (69), the thickness of the microcrystalline glass is 0.2 to 1 mm, preferably 0.3 to 0.9 mm, more preferably 0.5 to 0.8 mm, and further preferably 0.55 mm or 0.6 mm or 0.68 mm or 0.7 mm or 0.75 mm.
[0078] (71). The microcrystalline glass having a spinel crystal phase according to any one of (43) to (51), wherein the components, expressed in weight percentage, include: NiO: 0-4%; and / or Ni2O3: 0-4%; and / or CoO: 0-2%; and / or Co2O3: 0-2%; and / or Fe2O3: 0-7%; and / or MnO2: 0-4%; and / or Er2O3: 0-8%; and / or Nd2O3: 0-8%; and / or Cu2O: 0-4%; and / or Pr2O3: 0-8%; and / or CeO2: 0-4%.
[0079] (72) The glass-ceramics having a spinel crystal phase according to any one of (43) to (51), wherein the components, expressed in weight percentage, are: NiO: 0.1-4%; and / or Ni2O3: 0.1-4%; and / or CoO: 0.05-2%; and / or Co2O3: 0.05-2%; and / or Fe2O3: 0.2-7%; and / or MnO2: 0.1-4%; and / or Er2O3: 0.4-8%; and / or Nd2O3: 0.4-8%; and / or Cu2O: 0.5-4%; and / or Pr2O3: 0.4-8%; and / or CeO2: 0.5-4%.
[0080] (73). The microcrystalline glass having a spinel crystal phase according to any one of (43) to (51), wherein the components, expressed in weight percentage, contain: NiO: 0.1-3%; and / or Ni2O3: 0.1-3%; and / or CoO: 0.05-1.8%; and / or Co2O3: 0.05-1.8%; and / or Fe2O3: 0.2-5%; and / or MnO2: 0.1-3%; and / or Er2O3: 0.4-6%; and / or Nd2O3: 0.4-6%; and / or Cu2O: 0.5-3%; and / or Pr2O3: 0.4-6%; and / or CeO2: 0.5-3%.
[0081] (74) The glass-ceramics having a spinel crystal phase according to any one of (43) to (51), wherein the components thereof, expressed in weight percentage, contain: NiO: 0.1 to 3%; and / or Ni2O3: 0.1 to 3%.
[0082] (75) The glass-ceramics having a spinel crystal phase according to any one of (43) to (51), wherein the components, expressed in weight percentage, contain: CoO: 0.05 to 1.8%; and / or Co2O3: 0.05 to 1.8%.
[0083] (76) The glass-ceramics having a spinel crystal phase according to any one of (43) to (51), wherein the components thereof, expressed in weight percentage, contain: Cu2O: 0.5 to 3%; and / or CeO2: 0.5 to 3%.
[0084] (77). The microcrystalline glass having a spinel crystal phase according to any one of (43) to (51), wherein the components, expressed in weight percentage, are: Fe2O3: 0.2-5%, CoO: 0.05-0.3%; or Fe2O3: 0.2-5%, Co2O3: 0.05-0.3%; or Fe2O3: 0.2-5%, CoO: 0.05-0.3%, NiO: 0.1-1%; or Fe2O3: 0.2-5%, Co2O3: 0.05-0.3%, NiO: 0.1-1%.
[0085] (78). The microcrystalline glass having a spinel crystal phase according to any one of (43) to (51), wherein its components, expressed in weight percentage, contain: Pr2O3: 0.4 to 6%; or Fe2O3: 0.2 to 5%; or MnO2: 0.1 to 3%; or Er2O3: 0.4 to 6%; or Nd2O3: 0.4 to 6%.
[0086] (79). The microcrystalline glass having a spinel crystal phase according to any one of (43) to (51), wherein its components, expressed in weight percentage, contain: Er2O3: 0.4 to 6%, Nd2O3: 0.4 to 4%, and MnO2: 0.1 to 2%.
[0087] (80) A glass cover plate comprising the glass-ceramic product having a spinel crystal phase as described in any one of (1) to (42) and / or the glass-ceramic product having a spinel crystal phase as described in any one of (43) to (79).
[0088] (81) A glass component comprising a glass-ceramic product having a spinel crystal phase as described in any one of (1) to (42), and / or a glass-ceramic product having a spinel crystal phase as described in any one of (43) to (79).
[0089] (82) An electronic device comprising a glass-ceramic product having a spinel crystal phase as described in any one of (1) to (42), and / or a glass-ceramic product having a spinel crystal phase as described in any one of (43) to (79), and / or a glass cover as described in (80), and / or a glass component as described in (81).
[0090] (83) A display device comprising a glass-ceramic product having a spinel crystal phase as described in any one of (1) to (42), and / or a glass-ceramic product having a spinel crystal phase as described in any one of (43) to (79), and / or a glass cover plate as described in (80), and / or a glass component as described in (81).
[0091] (84). A method for manufacturing a glass-ceramic product having a spinel crystal phase as described in any one of (1) to (42), the method comprising the following steps: forming a matrix glass, subjecting the matrix glass to a crystallization process to form a glass-ceramic product having a spinel crystal phase, and then subjecting the glass-ceramic product having a spinel crystal phase to a chemical strengthening process to form a glass-ceramic product having a spinel crystal phase.
[0092] (85). According to the method for manufacturing a microcrystalline glass product having a spinel crystal phase as described in (84), the formation of the matrix glass includes the following steps: mixing the raw materials evenly according to the component ratio, then putting them into a crucible, and melting them in an electric furnace or a gas furnace at a temperature range of 1350 to 1550°C for 5 to 24 hours, preferably at a melting temperature of 1450 to 1550°C, and then clarifying, homogenizing, molding, and annealing to obtain the matrix glass, wherein the clarification temperature is greater than 1550°C but less than or equal to 1650°C, and the annealing temperature is 450 to 600°C.
[0093] (86). According to the method for manufacturing a microcrystalline glass product having a spinel crystal phase as described in (84), the crystallization process comprises the following steps: heating to a prescribed crystallization treatment temperature, maintaining the temperature for a certain period of time after reaching the crystallization treatment temperature, and then cooling down, the crystallization treatment temperature is 600 to 800°C, preferably 650 to 750°C, and the holding time at the crystallization treatment temperature is 1 to 10 hours, preferably 3 to 6 hours.
[0094] (87) According to the method for manufacturing a microcrystalline glass product having a spinel crystal phase as described in (84), the crystallization process includes the following steps: performing a nucleation process at a first temperature and then performing a crystal growth process at a second temperature.
[0095] (88). According to the method for manufacturing a microcrystalline glass product having a spinel crystal phase as described in (87), the crystallization process includes: the first temperature is 600-700°C, the second temperature is greater than 700°C but less than or equal to 800°C, the holding time at the first temperature is 1-6 hours, and the holding time at the second temperature is 2-5 hours.
[0096] (89). According to the method for manufacturing a microcrystalline glass product having a spinel crystal phase as described in (84), the chemical strengthening process comprises: immersing the microcrystalline glass having a spinel crystal phase in a salt bath of molten Na salt at 350 to 470°C for 1 to 36 hours, preferably in the temperature range of 400 to 460°C, and preferably in the time range of 2 to 15 hours; and / or immersing the microcrystalline glass having a spinel crystal phase in a mixed salt bath of molten K salt and Na salt at 360 to 450°C for 1 to 36 hours, preferably in the time range of 2 to 24 hours.
[0097] (90). A method for manufacturing a microcrystalline glass having a spinel crystal phase as described in any one of (43) to (79), the method comprising the following steps: forming a matrix glass, and then forming a microcrystalline glass having a spinel crystal phase through a crystallization process of the matrix glass.
[0098] (91). According to the method for manufacturing microcrystalline glass having a spinel crystal phase as described in (90), the formation of the matrix glass comprises the following steps: the raw materials are mixed evenly according to the component ratio, and then placed in a crucible, and melted in an electric furnace or a gas furnace at a temperature range of 1350 to 1550°C for 5 to 24 hours, preferably at a melting temperature of 1450 to 1550°C, and then the matrix glass is obtained after clarification, homogenization, molding, and annealing, wherein the clarification temperature is greater than 1550°C but less than or equal to 1650°C, and the annealing temperature is 450 to 600°C.
[0099] (92). According to the method for manufacturing microcrystalline glass having a spinel crystal phase as described in (90), the crystallization process comprises the following steps: heating to a prescribed crystallization treatment temperature, maintaining the temperature for a certain period of time after reaching the crystallization treatment temperature, and then cooling down, the crystallization treatment temperature is 600-800°C, preferably 650-750°C, and the holding time at the crystallization treatment temperature is 1-10 hours, preferably 3-6 hours.
[0100] (93) According to the method for manufacturing a microcrystalline glass product having a spinel crystal phase as described in (90), the crystallization process includes the following steps: performing a nucleation process at a first temperature and then performing a crystal growth process at a second temperature.
[0101] (94). According to the method for manufacturing a microcrystalline glass product having a spinel crystal phase as described in (93), the crystallization process includes: the first temperature is 600-700°C, the second temperature is greater than 700°C but less than or equal to 800°C, the holding time at the first temperature is 1-6 hours, and the holding time at the second temperature is 2-5 hours.
[0102] The beneficial effect of the present invention is that, through reasonable component design, the glass-ceramics with spinel crystal phase or the glass-ceramics products with spinel crystal phase obtained by the present invention have excellent light transmittance and mechanical properties. DETAILED DESCRIPTION
[0103] The glass-ceramics having a spinel crystal phase and the glass-ceramics products having a spinel crystal phase of the present invention are materials having a crystalline phase (sometimes also referred to as a crystal) and a glass phase. The crystalline phase of the glass-ceramics and the glass-ceramics products can be identified by the peak angle appearing in the X-ray diffraction pattern of the X-ray diffraction analysis and / or measured by TEMEDX.
[0104] After repeated experiments and studies, the inventors of the present invention have obtained the glass-ceramics with a spinel crystal phase or the glass-ceramics products with a spinel crystal phase of the present invention by regulating the content and content ratio of the specific components constituting the glass-ceramics with a spinel crystal phase and the glass-ceramics products with a spinel crystal phase to specific values and making them contain a specific crystal phase. In the present invention, the glass-ceramics with a spinel crystal phase is sometimes referred to as glass-ceramics, and the glass-ceramics products with a spinel crystal phase are sometimes referred to as glass-ceramics.
[0105] Next, the scope of each component (ingredient) of the matrix glass, microcrystalline glass and microcrystalline glass products of the present invention is described. In this specification, unless otherwise specified, the content of each component is expressed in weight percentage (wt%) relative to the total amount of matrix glass, microcrystalline glass or microcrystalline glass product material converted into oxide composition. Here, the "composition converted into oxide" means that when oxides, composite salts and hydroxides used as raw materials for the matrix glass, microcrystalline glass or microcrystalline glass product components of the present invention decompose and transform into oxides when melted, the total amount of the oxide material is taken as 100%. In addition, in this specification, when it is only referred to as glass, it is the matrix glass before crystallization (i.e., crystallization process treatment), the matrix glass after crystallization (i.e., crystallization process treatment) is called microcrystalline glass, and microcrystalline glass products refer to products obtained after chemical strengthening of microcrystalline glass.
[0106] Unless otherwise indicated in specific cases, the numerical ranges listed herein include upper and lower limits, and "above" and "below" include the endpoints, as well as all integers and fractions within the range, without limitation to the specific values listed when defining the range. The term "about" as used herein means that the formula, parameters and other quantities and features are not and need not be exact, and may be approximate and / or larger or lower if necessary, reflecting tolerances, conversion factors and measurement errors, etc. "And / or" as used herein is inclusive, for example, "A; and / or B" means only A, or only B, or both A and B.
[0107] In some embodiments of the present invention, the spinel crystal phase in the glass-ceramic or glass-ceramic product having a spinel crystal phase is preferably a zinc aluminum spinel crystal phase (ZnAl2O4). In some embodiments, the spinel crystal phase has a higher weight percentage than other crystal phases in the glass-ceramic or glass-ceramic product. In some embodiments, the weight percentage of the spinel crystal phase in the glass-ceramic or glass-ceramic product is 20 to 60%, preferably the weight percentage of the spinel crystal phase in the glass-ceramic or glass-ceramic product is 25 to 50%, more preferably the weight percentage of the spinel crystal phase in the glass-ceramic or glass-ceramic product is 25 to 45%, and further preferably the weight percentage of the spinel crystal phase in the glass-ceramic or glass-ceramic product is 30 to 45%. In some embodiments, the weight percentage of spinel crystalline phase in the microcrystalline glass or microcrystalline glass article is 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, or 60%.
[0108] In some embodiments of the present invention, the crystal phase in the glass-ceramic having a spinel crystal phase or the glass-ceramic product having a spinel crystal phase contains a quartz crystal phase (including quartz and quartz solid solution), preferably, the quartz crystal phase includes a β-quartz solid solution. In some embodiments, the weight percentage of the quartz crystal phase in the glass-ceramic or the glass-ceramic product is less than 20%, preferably the weight percentage of the quartz crystal phase in the glass-ceramic or the glass-ceramic product is less than 10%, more preferably the weight percentage of the quartz crystal phase in the glass-ceramic or the glass-ceramic product is less than 5%, and further preferably the glass-ceramic or the glass-ceramic product does not contain a quartz crystal phase. In some embodiments, the weight percentage of quartz crystal phase in the microcrystalline glass or microcrystalline glass article is 0%, greater than 0%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, or 20%.
[0109] SiO2 is a network former of the glass-ceramics and glass-ceramics products of the present invention. SiO2 can form a network structure using the structural components of silicon-oxygen tetrahedrons to form the basic structure of silicates. In some embodiments, SiO2 is also a necessary component for forming a quartz crystal phase. If the SiO2 content is too low, the chemical stability of the glass-ceramics and glass-ceramics products will deteriorate; if the SiO2 content is too high, the viscosity of the glass will be greatly increased, the melting temperature will be increased, the material will be difficult to smelt, and the difficulty of forming the matrix glass will increase. Therefore, the content of SiO2 in the present invention is 40-55%, preferably 45-53%, and more preferably 48-52%. In some embodiments, the SiO2 may include about 40%, 40.5%, 41%, 41.5%, 42%, 42.5%, 43%, 43.5%, 44%, 44.5%, 45%, 45.5%, 46%, 46.5%, 47%, 47.5%, 48%, 48.5%, 49%, 49.5%, 50%, 50.5%, 51%, 51.5%, 52%, 52.5%, 53%, 53.5%, 54%, 54.5%, 55%.
[0110] Al2O3 is beneficial to improving the mechanical properties and chemical stability of the microcrystalline glass and microcrystalline glass products of the present invention, and is also an essential component for forming the spinel crystal phase of the present invention. Al2O3 can form [AlO4] tetrahedrons, replacing part of [SiO4] tetrahedrons to form a network structure. The molecular volume of [AlO4] tetrahedron is 41cm 3 / mol, the molecular volume of [SiO4] tetrahedron is 27.2 cm 3 / mol, after replacing part of the [SiO4] tetrahedron with [AlO4] tetrahedron, the molecular volume increases and the structural network space expands, which is beneficial to the diffusion of alkali metal ions during chemical strengthening and is also conducive to the acceptance of a large amount of Na + , promoting ion exchange. If the Al2O3 content is too low, it is not conducive to the improvement of the strengthening effect and the precipitation of crystals, and the mechanical properties and chemical stability of the glass are poor. If the Al2O3 content is too high, the glass will be difficult to melt, the melting temperature will be high, and stones will easily precipitate on the surface during molding. Therefore, the Al2O3 content is 15-30%, preferably 18-25%, and more preferably 20-23%. In some embodiments, about 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, 25%, 25.5%, 26%, 26.5%, 27%, 27.5%, 28%, 28.5%, 29%, 29.5%, 30% Al2O3 may be included.
[0111] In some embodiments, the ratio of SiO2 to Al2O3 is controlled within the range of 1.5 to 3.2, which is beneficial to improving the drop ball test height and four-point bending strength of the microcrystalline glass and microcrystalline glass products, and improving the ion exchange layer depth and surface stress of the microcrystalline glass products. Therefore, preferably SiO2 / Al2O3 is 1.5 to 3.2, more preferably SiO2 / Al2O3 is 1.7 to 3.0, further preferably SiO2 / Al2O3 is 1.8 to 2.8, and further preferably SiO2 / Al2O3 is 2.0 to 2.5. In some embodiments, the value of SiO2 / Al2O3 is 1.5, 1.55, 1.6, 1.65, 1.7, 1.75, 1.8, 1.85, 1.9, 1.95, 2.0, 2.05, 2.1, 2.15, 2.2, 2.25, 2.3, 2.35, 2.4, 2.45, 2.5, 2.55, 2.6, 2.65, 2.7, 2.75, 2.8, 2.85, 2.9, 2.95, 3.0, 3.05, 3.1, 3.15, 3.2.
[0112] Li2O can lower the melting point of glass, and is also a necessary component for participating in chemical strengthening and improving the mechanical properties of microcrystalline glass products. On the other hand, Li2O can provide free oxygen and reduce TiO2 coloring. If the Li2O content is too high, the crystals in microcrystalline glass and microcrystalline glass products will grow easily, and the crystal growth will be unstable, which will affect the transmittance of microcrystalline glass and microcrystalline glass products and make the chemical stability worse. Therefore, the content of Li2O is 0.1-6%, preferably 1-5%, and more preferably 2-4%. In some embodiments, about 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, and 6% Li2O may be included.
[0113] ZnO is a necessary component for forming the spinel crystal phase in the present invention. The spinel crystal phase content can be regulated by controlling the content of ZnO and Al2O3, taking into account the transmittance while ensuring the mechanical strength. If the ZnO content is low, the crystal phase content in the microcrystalline glass and microcrystalline glass products is low, and the mechanical properties such as Vickers hardness and Young's modulus are poor. If the ZnO content is too high, the residual Zn in the glass phase 2+ It hinders ion exchange during chemical strengthening and is not conducive to obtaining high-performance microcrystalline glass products. Therefore, the content of ZnO is 9-20%, preferably 11-18%, and more preferably 12-16%. In some embodiments, about 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20% ZnO may be included.
[0114] In some embodiments, controlling the total content of Al2O3 and ZnO (Al2O3+ZnO) within the range of 26-45% is beneficial for obtaining the desired content of spinel crystal phase in the glass-ceramics and glass-ceramics products, and preventing the surface stress of the glass-ceramics products from deteriorating while improving the drop resistance and drop ball test height of the glass-ceramics and glass-ceramics products. Therefore, preferably, Al2O3+ZnO is 26-45%, more preferably, Al2O3+ZnO is 30-42%, further preferably, Al2O3+ZnO is 32-42%, and further preferably, Al2O3+ZnO is 35-40%. In some embodiments, the Al2O3 + ZnO is 26%, 26.5%, 27%, 27.5%, 28%, 28.5%, 29%, 29.5%, 30%, 30.5%, 31%, 31.5%, 32%, 32.5%, 33%, 33.5%, 34%, 34.5%, 35%, 35.5%, 36%, 36.5%, 37%, 37.5%, 38%, 38.5%, 39%, 39.5%, 40%, 40.5%, 41%, 41.5%, 42%, 42.5%, 43%, 43.5%, 44%, 44.5%, 45%.
[0115] In some embodiments, controlling the ratio of Al2O3 to ZnO content Al2O3 / ZnO in the range of 1.0 to 3.0 is beneficial to improving the hardness of glass-ceramics and glass-ceramics products, optimizing Young's modulus, and preventing the transmittance of glass-ceramics and glass-ceramics products from decreasing and the haze from deteriorating. Therefore, Al2O3 / ZnO is preferably 1.0 to 3.0, more preferably 1.2 to 2.8, further preferably 1.25 to 2.5, and further preferably 1.5 to 2.3. In some embodiments, the Al2O3 / ZnO is 1.0, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5, 1.55, 1.6, 1.65, 1.7, 1.75, 1.8, 1.85, 1.9, 1.95, 2.0, 2.05, 2.1, 2.15, 2.2, 2.25, 2.3, 2.35, 2.4, 2.45, 2.5, 2.55, 2.6, 2.65, 2.7, 2.75, 2.8, 2.85, 2.9, 2.95, 3.0.
[0116] TiO2 is a nucleating agent for the glass-ceramics and glass-ceramics products of the present invention. If the TiO2 content is too high, the glass-ceramics and glass-ceramics products will be severely colored (brown-yellow), and the transmittance of the glass-ceramics and glass-ceramics products in the visible light region will be reduced, and the haze and |B| value will increase. In addition, if the TiO2 content is too high, the glass will easily become milky during molding and crystallization, making the glass opaque. Therefore, the content of TiO2 in the present invention is 0.5-7%, preferably 1-6%, and more preferably 2-5%. In some embodiments, about 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, and 7% TiO2 may be included.
[0117] In some embodiments, the ratio of Li2O content to TiO2 content (Li2O / TiO2) is controlled within the range of 0.2 to 4.5, which can effectively reduce the Ti content in the microcrystalline glass and microcrystalline glass products. 3+ The coloring of ions improves the transmittance of microcrystalline glass and microcrystalline glass products, and optimizes the haze and |B| value of microcrystalline glass and microcrystalline glass products. Therefore, the preferred Li2O / TiO2 is 0.2 to 4.5, the more preferred Li2O / TiO2 is 0.5 to 3.5, the further preferred Li2O / TiO2 is 0.7 to 2.5, and the further preferred Li2O / TiO2 is 0.75 to 1.5. In some embodiments, the Li2O / TiO2 is 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5, 1. 55, 1.6, 1.65, 1.7, 1.75, 1.8, 1.85, 1.9, 1.95, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5.
[0118] In some embodiments, the ratio (TiO2+ZnO) / Al2O3 between the total content of TiO2 and ZnO TiO2+ZnO and the content of Al2O3 is controlled within the range of 0.4 to 1.5, which can optimize the chemical strengthening performance of microcrystalline glass, increase the depth of the ion exchange layer of microcrystalline glass products, and improve the fracture toughness, four-point bending strength and drop ball test height. Therefore, preferably (TiO2+ZnO) / Al2O3 is 0.4 to 1.5, more preferably (TiO2+ZnO) / Al2O3 is 0.5 to 1.2, further preferably (TiO2+ZnO) / Al2O3 is 0.6 to 1.0, and further preferably (TiO2+ZnO) / Al2O3 is 0.6 to 0.9. In some embodiments, (TiO2+ZnO) / Al2O3 is 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5.
[0119] ZrO2 can be used as a nucleating agent for microcrystalline glass and microcrystalline glass products. When used together with TiO2, it can make the microcrystalline glass have as many nuclei as possible. When there are more nuclei, it is conducive to stable crystal growth and uniform grain size. If the ZrO2 content is too high, the melting of the glass will be more difficult. Therefore, the content of ZrO2 is 0 to 5%, preferably 0.5 to 4%, and more preferably 1 to 3%. In some embodiments, it may contain about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5% ZrO2.
[0120] ZrO2 has a low solubility in the glass system of the present invention. In some embodiments, the solubility of ZrO2 in the glass can be increased by containing a certain amount of P2O5; however, if too much P2O5 is contained, the glass is easily separated during molding, resulting in reduced chemical stability of the microcrystalline glass and microcrystalline glass products. Therefore, the content of P2O5 in the present invention is 0-5%, preferably 0.5-4%, and more preferably 1-3%. In some embodiments, it may contain about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5% P2O5.
[0121] In some embodiments, the ratio (Al2O3+Li2O) / P2O5 between the total content of Al2O3 and Li2O Al2O3+Li2O and the content of P2O5 is controlled within the range of 5.0 to 45.0, which is beneficial to improving the four-point bending strength and drop resistance of the microcrystalline glass and microcrystalline glass products, and improving the surface stress of the microcrystalline glass products. Therefore, it is preferred that (Al2O3+Li2O) / P2O5 is 5.0 to 45.0, more preferably (Al2O3+Li2O) / P2O5 is 7.0 to 35.0, further preferably (Al2O3+Li2O) / P2O5 is 8.0 to 30.0, and further preferably (Al2O3+Li2O) / P2O5 is 10.0 to 25.0. In some embodiments, (Al2O3 + Li2O) / P2O5 is 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0, 15.5, 16.0, 16.5, 17.0, 17.5, 18.0, 18.5, 19.0 , 19.5, 20.0, 20.5, 21.0, 21.5, 22.0, 22.5, 23.0, 23.5, 24.0, 24.5, 25.0, 26.0, 27.0, 28.0, 29.0, 30.0, 31.0, 32.0, 33.0, 34.0, 35.0, 36.0, 37.0, 38.0, 39.0, 40.0, 41.0, 42.0, 43.0, 44.0, 45.0.
[0122] In some embodiments, controlling the total content of P2O5 and ZrO2 (P2O5+ZrO2) within the range of 0-8% is beneficial for obtaining uniform grains and smaller grain sizes in the microcrystalline glass and microcrystalline glass products, and optimizing the transmittance of the microcrystalline glass and microcrystalline glass products. Therefore, preferably, P2O5+ZrO2 is 0-8%, more preferably, P2O5+ZrO2 is 0.1-7%, and further preferably, P2O5+ZrO2 is 0.5-5%. In some embodiments, P2O5+ZrO2 is 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6. %, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6%, 6.1%, 6.2%, 6.3%, 6.4%, 6.5%, 6.6%, 6.7%, 6.8%, 6.9%, 7%, 7.1%, 7.2%, 7.3%, 7.4%, 7.5%, 7.6%, 7.7%, 7.8%, 7.9%, 8%.
[0123] In some embodiments, controlling the ratio of the content of P2O5 to the content of ZrO2, P2O5 / ZrO2, within the range of 0.1 to 5.0 is beneficial to improving the hardness and fracture toughness of the microcrystalline glass and microcrystalline glass products, and preventing the drop resistance and Young's modulus from deteriorating. Therefore, preferably P2O5 / ZrO2 is 0.1 to 5.0, more preferably P2O5 / ZrO2 is 0.2 to 3.0, further preferably P2O5 / ZrO2 is 0.5 to 2.0, and further preferably P2O5 / ZrO2 is 0.6 to 1.5. In some embodiments, P2O5 / ZrO2 is 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0.
[0124] MgO helps to reduce the viscosity of the glass, inhibits glass crystallization during molding and refines the grains during crystallization, and also has the effect of improving low-temperature solubility. In some embodiments, MgO has the effect of promoting the formation of quartz solid solution crystalline phase. If the MgO content is too high, a quartz solid solution crystalline phase is easily generated during glass crystallization, and the quartz solid solution crystalline phase has larger grains, which will reduce the transmittance of microcrystalline glass and microcrystalline glass products. Therefore, the content of MgO is 0.1-6%, preferably 1-5%, and more preferably 2-4%. In some embodiments, the present invention may comprise about 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9 %, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6% MgO.
[0125] In some embodiments, the ratio (Li2O+MgO) / TiO2 between the total content of Li2O and MgO Li2O+MgO and the content of TiO2 is controlled within the range of 0.3 to 8.0, which can refine the grains, improve the transmittance and drop resistance of the microcrystalline glass and microcrystalline glass products, and optimize the haze and |B| value of the microcrystalline glass and microcrystalline glass products. Therefore, preferably (Li2O+MgO) / TiO2 is 0.3 to 8.0, more preferably (Li2O+MgO) / TiO2 is 0.5 to 5.0, further preferably (Li2O+MgO) / TiO2 is 1.0 to 3.0, and further preferably (Li2O+MgO) / TiO2 is 1.2 to 2.5. In some embodiments, (Li2O+MgO) / TiO2 is 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8 , 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.1, 7.2, 7.3, 7.4, 7.5, 7.6, 7.7, 7.8, 7.9, 8.0.
[0126] In some embodiments, the ratio of the content of Al2O3 to the total content of MgO and TiO2 (MgO+TiO2) (Al2O3 / (MgO+TiO2)) is controlled within the range of 1.3 to 10.0, which is beneficial to improving the hardness and drop ball test height of microcrystalline glass and microcrystalline glass products, and optimizing the surface stress and haze of microcrystalline glass products. Therefore, preferably Al2O3 / (MgO+TiO2) is 1.3 to 10.0, more preferably Al2O3 / (MgO+TiO2) is 1.5 to 8.0, further preferably Al2O3 / (MgO+TiO2) is 2.5 to 6.5, and further preferably Al2O3 / (MgO+TiO2) is 3.0 to 5.5. In some embodiments, Al2O3 / (MgO+TiO2) is 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3 , 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.1, 7.2, 7.3, 7.4, 7.5, 7.6, 7.7, 7.8, 7.9, 8.0, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7, 8.8, 8.9, 9.0, 9.1, 9.2, 9.3, 9.4, 9.5, 9.6, 9.7, 9.8, 9.9, 10.0.
[0127] B2O3 helps melt the glass and improves the melting effect of the glass. If the B2O3 content is too high, the chemical stability of the glass will deteriorate, and boron anomaly will easily occur, and the boron oxygen tetrahedron will transform into a boron oxygen triangle structure, and the viscosity of the glass will decrease. In addition, boron volatilization will easily form stripes, causing uneven glass. Therefore, the content of B2O3 is 0-4%, preferably 0-2%, and more preferably 0-1%. In some embodiments, about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4% B2O3 may be included.
[0128] Na2O can promote glass melting and improve the chemical strengthening performance of microcrystalline glass. However, if too much Na2O is contained in the present invention, it is easy to cause more glass break bonds, reduce the strength of the matrix glass, and affect the strength of microcrystalline glass and microcrystalline glass products. Therefore, the upper limit of the Na2O content in the present invention is 6%, preferably 4%, and more preferably 2%. In some embodiments, it may contain about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7% , 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6% Na2O.
[0129] In some embodiments, the ratio (SiO2+Na2O) / ZnO between the total content of SiO2 and Na2O SiO2+Na2O and the content of ZnO is controlled within the range of 2.2 to 6.2, which can improve the fracture toughness and compressive strength of the microcrystalline glass and microcrystalline glass products while optimizing the |B| value. Therefore, preferably (SiO2+Na2O) / ZnO is 2.2 to 6.2, more preferably (SiO2+Na2O) / ZnO is 2.5 to 6.0, further preferably (SiO2+Na2O) / ZnO is 2.8 to 5.5, and further preferably (SiO2+Na2O) / ZnO is 3.0 to 5.0. In some embodiments, (SiO2 + Na2O) / ZnO is 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2.
[0130] K2O helps to reduce the glass melting temperature, is beneficial to chemical strengthening, and can increase the depth of the ion exchange layer of the microcrystalline glass product; however, if too much K2O is contained, it is easy to cause a decrease in the chemical stability of the glass and a decrease in hardness. Therefore, the content of K2O is 3% or less, preferably 2% or less, and more preferably 1% or less. In some embodiments, about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3% K2O may be included.
[0131] In some embodiments, the ratio of the total content of Na2O and K2O Na2O+K2O to the content of ZnO (Na2O+K2O) / ZnO is controlled to be below 0.8, which can refine the grains, reduce the grain size of the microcrystalline glass and microcrystalline glass products, improve the transmittance and anti-extrusion strength of the microcrystalline glass and microcrystalline glass products, and optimize the haze of the microcrystalline glass and microcrystalline glass products. Therefore, it is preferred that (Na2O+K2O) / ZnO is below 0.8, more preferably (Na2O+K2O) / ZnO is below 0.6, further preferably (Na2O+K2O) / ZnO is below 0.4, and further preferably (Na2O+K2O) / ZnO is below 0.2. In some embodiments, (Na2O+KO) / ZnO is 0, greater than 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8.
[0132] CaO, BaO and SrO as co-solvents do not participate in the formation of the crystal phase, but remain in the residual glass phase of the microcrystalline glass, which is beneficial to reduce the melting temperature and processing temperature. However, too high a content will damage the nucleation and crystallization in the process of transforming the matrix glass into microcrystalline glass, and have an adverse effect on the chemical stability of the microcrystalline glass. Therefore, the total content of CaO, BaO and SrO CaO+BaO+SrO is 0-5%, preferably 0-4%, and more preferably 0-2%. In some embodiments, CaO+BaO+SrO is 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1 %, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%.
[0133] Y2O3 can promote the melting of ZrO2 and reduce the difficulty of melting glass. When the content is too much, it will make it difficult to form crystals when the glass is crystallized, and the drop ball test height of microcrystalline glass and microcrystalline glass products will decrease. Therefore, the upper limit of the Y2O3 content is 6%, preferably the upper limit is 4%, and more preferably the upper limit is 2%. In some embodiments, it may contain about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7% , 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6% Y2O3.
[0134] In some embodiments, the glass, glass-ceramic or glass-ceramic product may also contain 0-2% of a clarifier to improve the defoaming ability of the glass, glass-ceramic or glass-ceramic product. Such clarifiers include, but are not limited to, one or more of Sb2O3, SnO2, SnO, CeO2, F (fluorine) compounds, Cl (chlorine) compounds and Br (bromine) compounds, preferably Sb2O3 as a clarifier. When the above-mentioned clarifiers exist alone or in combination, the upper limit of their content is preferably 2%, more preferably 1%, and further preferably 0.5%. In some embodiments, one or more of the clarifiers is present in an amount of about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%.
[0135] Without affecting the performance of the glass, glass-ceramic or glass-ceramic product of the present invention, other components not mentioned above, such as La2O3, Gd2O3, Yb2O3, Nb2O5, WO3, Bi2O3, Ta2O5, TeO2, etc., may be appropriately added. However, in order to maintain the excellent performance of the glass, glass-ceramic or glass-ceramic product of the present invention, the individual content or the total content of La2O3, Gd2O3, Yb2O3, Nb2O5, WO3, Bi2O3, Ta2O5, TeO2 is preferably 5% or less, more preferably 2% or less, further preferably 1% or less, and further preferably no content.
[0136] PbO and As2O3 are toxic substances, and even a small amount of them does not meet the requirements of environmental protection. Therefore, in some embodiments of the present invention, it is preferred that PbO and / or As2O3 are not contained.
[0137] In some embodiments of the present invention, a matrix glass, glass-ceramic or glass-ceramic product with color can be prepared by containing a colorant, and the matrix glass, glass-ceramic or glass-ceramic product can present different colors, and the colorant contains: NiO: 0-4%; and / or Ni2O3: 0-4%; and / or CoO: 0-2%; and / or Co2O3: 0-2%; and / or Fe2O3: 0-7%; and / or MnO2: 0-4%; and / or Er2O3: 0-8%; and / or Nd2O3: 0-8%; and / or Cu2O: 0-4%; and / or Pr2O5: 0-8%; and / or CeO2: 0-4%. The weight percentage content of the colorant and its function are described in detail as follows:
[0138] The brown or green matrix glass, glass-ceramic or glass-ceramic product prepared by the present invention uses NiO, Ni2O3 or Pr2O5 as a colorant. NiO and Ni2O3 are colorants used to prepare brown or green matrix glass, glass-ceramic or glass-ceramic products. The two components can be used alone or in combination. The content of each component is generally less than 4%, preferably less than 3%. If the content exceeds 4%, the colorant cannot be well dissolved in the matrix glass, glass-ceramic or glass-ceramic product. The lower limit of each content is more than 0.1%. If it is less than 0.1%, the color of the matrix glass, glass-ceramic or glass-ceramic product is not obvious. In some embodiments, about 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0% NiO or Ni2O3 may be included. When used in combination, the total amount of NiO and Ni2O3 is generally less than 4%, and the lower limit of the total amount is above 0.1%. In some embodiments, about 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0% NiO and Ni2O3 may be included. Pr2O5 is used as a colorant for green matrix glass, microcrystalline glass or microcrystalline glass products. It is used alone, and the content is generally less than 8%, preferably less than 6%. The lower limit of the content is above 0.4%. If it is less than 0.4%, the color of the matrix glass, microcrystalline glass or microcrystalline glass products will not be obvious.In some embodiments, about 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%, 4.2%, 4.4%, 4.6%, 4.8%, 5.0%, 5.2%, 5.4%, 5.6%, 5.8%, 6.0%, 6.2%, 6.4%, 6.6%, 6.8%, 7.0%, 7.2%, 7.4%, 7.6%, 7.8%, 8.0% Pr2O5 may be included.
[0139] The blue matrix glass, glass-ceramic or glass-ceramic product prepared by the present invention uses CoO or Co2O3 as a colorant. The two colorant components can be used alone or in combination. The respective contents are generally less than 2%, preferably less than 1.8%. If the content exceeds 2%, the colorant cannot be well dissolved in the matrix glass, glass-ceramic or glass-ceramic product. The respective lower limits of the contents are above 0.05%. If the content is less than 0.05%, the color of the matrix glass, glass-ceramic or glass-ceramic product is not obvious. In some embodiments, about 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0% of CoO or Co2O3 may be included. When used in combination, the total amount of CoO and Co2O3 does not exceed 2%, and the lower limit of the total amount is above 0.05%. In some embodiments, about 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0% of CoO and Co2O3 may be included.
[0140] The yellow matrix glass, glass-ceramics or glass-ceramics products prepared by the present invention use Cu2O or CeO2 as a colorant. The two colorant components are used alone or in combination, and the lower limits of their respective contents are above 0.5%. If the content is below 0.5%, the color of the matrix glass, glass-ceramics or glass-ceramics products is not obvious. The content of Cu2O used alone is below 4%, preferably below 3%. If the content exceeds 4%, the matrix glass is easily crystallized. In some embodiments, about 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0% Cu2O may be included. The CeO2 content alone is generally 4% or less, preferably 3% or less. If the content exceeds 4%, the matrix glass, microcrystalline glass or microcrystalline glass product has poor gloss. In some embodiments, about 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0% of CeO2 may be included. Meanwhile, a small amount of CeO2 added to the glass has a defoaming effect. CeO2 can also be used as a clarifier in the glass. When used as a clarifier, its content is less than 2%, preferably less than 1%, and more preferably less than 0.5%. If two colorants are mixed, the total amount is generally less than 4%, and the lower limit of the total amount is above 0.5%. In some embodiments, about 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0% of CeO2 and Cu2O may be included.
[0141] The black or smoke gray matrix glass, glass-ceramics or glass-ceramics products prepared by the present invention use Fe2O3 alone as a colorant; or use a mixture of Fe2O3 and CoO as a colorant; or use a mixture of Fe2O3 and Co2O3 as a colorant; or use a mixture of Fe2O3, CoO and NiO as a colorant; or use a mixture of Fe2O3, Co2O3 and NiO as a colorant. The colorant used to prepare black and smoke gray matrix glass, glass-ceramics or glass-ceramics products mainly uses Fe2O3 for coloring, and the content is less than 7%, preferably less than 5%, and the lower limit of its content is more than 0.2%. In some embodiments, it may contain about 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6% , 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0% of Fe2O3. CoO and Co2O3 have absorption in visible light and can deepen the coloring of matrix glass, microcrystalline glass or microcrystalline glass products. Generally, when mixed with Fe2O3, their respective contents are less than 0.6%, and the lower limit is above 0.2%. In some embodiments, CoO and / or Co2O3 may be included in an amount of about 0.2%, 0.3%, 0.4%, 0.5%, or 0.6%. NiO absorbs visible light and can deepen the coloring of the matrix glass, glass-ceramics, or glass-ceramics products. Generally, when mixed, its content is less than 1%, and the lower limit of the total amount is more than 0.2%. In some embodiments, NiO may be included in an amount of about 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, or 1.0%.
[0142] The purple matrix glass, microcrystalline glass or microcrystalline glass products prepared by the present invention use MnO2 as a colorant, and the content is generally less than 4%, preferably less than 3%, and the lower limit of the content is above 0.1%. If it is less than 0.1%, the color of the matrix glass, microcrystalline glass or microcrystalline glass products is not obvious. In some embodiments, about 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0% MnO2 may be included.
[0143] The pink matrix glass, glass-ceramics or glass-ceramics products prepared by the present invention use Er2O3 as a colorant, and the content of Er2O3 is generally below 8%, preferably below 6%. Since the coloring efficiency of the rare earth element Er2O3 is low, when the content exceeds 8%, the color of the matrix glass, glass-ceramics or glass-ceramics products cannot be further deepened, but the cost is increased. The lower limit of the content is above 0.4%. If it is less than 0.4%, the color of the matrix glass, glass-ceramics or glass-ceramics products is not obvious. In some embodiments, about 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%, 4.2%, 4.4%, 4.6%, 4.8%, 5.0%, 5.2%, 5.4%, 5.6%, 5.8%, 6.0%, 6.2%, 6.4%, 6.6%, 6.8%, 7.0%, 7.2%, 7.4%, 7.6%, 7.8%, 8.0% Er2O3 may be included.
[0144] The purple-red matrix glass, glass-ceramics or glass-ceramics products prepared by the present invention use Nd2O3 as a colorant, and the content of Nd2O3 is generally below 8%, preferably below 6%. Since the rare earth element Nd2O3 has low coloring efficiency, even if the content exceeds 8%, the color of the matrix glass, glass-ceramics or glass-ceramics products cannot be further deepened, but the cost is increased. The lower limit of the content is above 0.4%. If it is less than 0.4%, the color of the matrix glass, glass-ceramics or glass-ceramics products is not obvious. In some embodiments, about 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%, 4.2%, 4.4%, 4.6%, 4.8%, 5.0%, 5.2%, 5.4%, 5.6%, 5.8%, 6.0%, 6.2%, 6.4%, 6.6%, 6.8%, 7.0%, 7.2%, 7.4%, 7.6%, 7.8%, 8.0% Nd2O3 may be included.
[0145] The red matrix glass, microcrystalline glass or microcrystalline glass products prepared by the present invention use a mixed colorant of Er2O3, Nd2O3 and MnO2. The Er ions in the glass absorb at 400-500nm, the Mn ions mainly absorb at 500nm, and the Nd ions mainly have strong absorption at 580nm. The mixture of the three substances can be used to prepare red matrix glass, microcrystalline glass or microcrystalline glass products. Since Er2O3 and Nd2O3 are rare earth colored, their coloring ability is relatively weak. The usage amount of Er2O3 is within 6%, the usage amount of Nd2O3 is within 4%, and the coloring of MnO2 is strong, and the usage amount is within 2%. The lower limit of the total amount of the mixed colorant used is above 0.9%.
[0146] The "does not contain" and "0%" recorded in this article mean that the compound, molecule or element is not intentionally added as a raw material to the matrix glass, microcrystalline glass or microcrystalline glass product of the present invention; however, as raw materials and / or equipment for producing matrix glass, microcrystalline glass or microcrystalline glass products, there will be certain impurities or components that are not intentionally added, which will be contained in small amounts or trace amounts in the final matrix glass, microcrystalline glass or microcrystalline glass product, and this situation is also within the scope of protection of the patent of this invention.
[0147] The grain size and crystalline phase type in the glass-ceramics or glass-ceramics products of the present invention will affect the haze and light transmittance of the glass-ceramics or glass-ceramics products. The smaller the grains, the higher the light transmittance; the smaller the haze, the higher the light transmittance. In some embodiments, the haze of the glass-ceramics products or glass-ceramics with a thickness of less than 1 mm is less than 0.3%, preferably less than 0.25%, and more preferably 0.05-0.2%. In some embodiments, the grain size of the glass-ceramics products or glass-ceramics is less than 60 nm, preferably less than 45 nm, and more preferably 10-30 nm.
[0148] In some embodiments, the crystalline phase content and refractive index in the glass-ceramics or glass-ceramics products of the present invention affect the |B| value of the glass-ceramics or glass-ceramics products. When observed in the visible light range, the glass-ceramics or glass-ceramics products appear bluish or yellowish, affecting the optical properties of the product, which is indicated by the |B| value in LAB (chromaticity value of material color). The glass-ceramics or glass-ceramics products of the present invention present a low |B| value in the visible light range. In some embodiments, the average optical |B| value of 400-800nm for glass-ceramics products or glass-ceramics with a thickness of less than 1 mm is less than 1.0, preferably less than 0.8, and more preferably 0.3-0.6.
[0149] In some embodiments, the glass-ceramics or glass-ceramics products of the present invention exhibit high transparency in the visible light range (i.e., the glass-ceramics or glass-ceramics products are transparent). Glass-ceramics or glass-ceramics products exhibit high transmittance in the visible light range. In some embodiments, the average light transmittance of glass-ceramics products with a thickness of less than 1 mm or glass-ceramics at 400 to 800 nm is preferably 87.0% or more, more preferably 88.5% or more, and further preferably 89.5% or more. In some preferred embodiments, the light transmittance of glass-ceramics products with a thickness of less than 1 mm or glass-ceramics at 550 nm is preferably 87.0% or more, more preferably 88.0% or more, and further preferably 89.0% or more.
[0150] In some embodiments, an antimicrobial component can be added to the matrix glass, glass-ceramic, or glass-ceramic product. The glass-ceramic or glass-ceramic product described herein can be used in applications such as kitchen or dining countertops, where exposure to harmful bacteria is likely. The antimicrobial components contained in the matrix glass, glass-ceramic, or glass-ceramic product include but are not limited to Ag, AgO, Cu, CuO, Cu2O, etc. In some embodiments, the content of the above antimicrobial components alone or in combination is less than 2%, preferably less than 1%.
[0151] The matrix glass, the glass-ceramics having a spinel crystal phase, and the glass-ceramics products having a spinel crystal phase of the present invention can be produced and manufactured by the following method:
[0152] Generating matrix glass: Mix the raw materials (oxides, hydroxides, composite salts, etc.) uniformly according to the component ratio, then put them into a crucible (e.g., a platinum or quartz crucible), and melt them in an electric furnace or a gas furnace at a temperature range of 1350 to 1550° C. for 5 to 24 hours according to the melting difficulty of the glass composition, preferably at a melting temperature of 1450 to 1550° C.; then clarify, homogenize, shape, and anneal to obtain the matrix glass. The clarifying temperature is preferably greater than 1550° C. but less than or equal to 1650° C., and the annealing temperature is preferably 450 to 600° C.
[0153] The matrix glass of the present invention can be formed by a well-known method.
[0154] The matrix glass of the present invention is crystallized by a crystallization process after molding or molding processing, and crystals are uniformly precipitated inside the glass to make glass-ceramics. The crystallization process can be carried out in one stage or in two stages, preferably in two stages. The two stages of crystallization process are to carry out the process of nucleation process at the first temperature, and then to carry out the process of crystal growth process at the second temperature. The crystallization process carried out at the first temperature is referred to as the first crystallization process, and the crystallization process carried out at the second temperature is referred to as the second crystallization process.
[0155] In order to obtain the desired physical and chemical properties of glass-ceramics, the preferred crystallization process is:
[0156] The above-mentioned crystallization treatment is carried out in one stage, and the nucleation process and the crystal growth process can be carried out continuously. That is, the temperature is raised to a specified crystallization treatment temperature, and after reaching the crystallization treatment temperature, the temperature is maintained for a certain period of time, and then the temperature is lowered. The crystallization treatment temperature is preferably 600 to 800°C, and in order to precipitate the desired crystalline phase, it is more preferably 650 to 750°C. The holding time at the crystallization treatment temperature is preferably 1 to 10 hours, and more preferably 3 to 6 hours.
[0157] When the crystallization treatment is carried out in two stages, the first temperature is preferably 600-700°C, the second temperature is preferably greater than 700°C but less than or equal to 800°C, the holding time at the first temperature is preferably 1-6 hours, and the holding time at the second temperature is preferably 2-5 hours.
[0158] In some embodiments, the matrix glass or glass-ceramics described herein can be manufactured into a formed body by various processes, including but not limited to sheets, and the processes include but are not limited to slit drawing, float process, rolling and other processes for forming sheets known in the art. Alternatively, the matrix glass or glass-ceramics can be formed by a float process or rolling process known in the art. The formed body of the present invention also includes lenses, prisms, etc.
[0159] The matrix glass or glass-ceramics of the present invention can be used to manufacture a glass molded body or a glass-ceramics molded body in the form of a sheet by grinding or polishing, but the method for manufacturing a glass molded body or a glass-ceramics molded body is not limited to these methods.
[0160] The matrix glass or microcrystalline glass of the present invention can be prepared into glass molded bodies or microcrystalline glass molded bodies of various shapes by using a heat bending process or a press process at a certain temperature, but is not limited to these methods.
[0161] In some embodiments, a glass forming body or a glass-ceramic forming body can be formed by a heat bending process. The heat bending process is a process in which 2D or 2.5D glass or glass-ceramic is placed in a mold and a heat bending machine is used to perform steps including heating preheating, pressurizing, and cooling to obtain a 3D curved glass forming body or glass-ceramic forming body.
[0162] In some embodiments, the glass-ceramic forming body has a 2.5D or 3D configuration, i.e., the glass-ceramic forming body has a non-planar configuration. As used herein, "non-planar configuration" means that in a 2.5D or 3D shape, at least a portion of the glass-ceramic forming body extends outward or along an angle with a plane defined by the original, laid-out configuration of the 2D matrix glass. A 2.5D or 3D glass-ceramic forming body formed from a matrix glass may have one or more protrusions or curved portions.
[0163] The matrix glass, the glass-ceramic having a spinel crystalline phase, and the glass-ceramic article having a spinel crystalline phase described in the present invention can have any reasonable and useful thickness.
[0164] In addition to improving mechanical properties by crystallization, the microcrystalline glass having a spinel crystal phase of the present invention can also obtain more excellent mechanical properties by forming a compressive stress layer, thereby manufacturing a microcrystalline glass product having a spinel crystal phase.
[0165] In some embodiments, the matrix glass or glass-ceramics can be processed into sheets, and / or shaped (such as punching, hot bending, etc.), polished and / or swept after shaping, and then chemically strengthened through a chemical strengthening process.
[0166] The chemical strengthening described in the present invention is an ion exchange method. During the ion exchange process, smaller metal ions in the matrix glass or glass-ceramics are replaced or "exchanged" by larger metal ions with the same valence state near the matrix glass or glass-ceramics. The larger ions replace the smaller ions, and compressive stress is built in the matrix glass or glass-ceramics to form a compressive stress layer.
[0167] In some embodiments, the metal ion is a monovalent alkali metal ion (e.g., Na + , K+ , Rb + , Cs + Ion exchange is performed by immersing the matrix glass or glass-ceramic in a salt bath containing at least one molten salt of a larger metal ion, which is used to replace the smaller metal ions in the matrix glass. Alternatively, other monovalent metal ions such as Ag + , Tl + , Cu + The one or more ion exchange processes used to chemically strengthen the matrix glass or glass-ceramic may include, but are not limited to, immersing it in a single salt bath, or immersing it in multiple salt baths of the same or different compositions with washing and / or annealing steps between immersions.
[0168] In some embodiments, the matrix glass or glass-ceramic can be ion exchanged by immersing in a salt bath of molten Na salt (such as NaNO3) at a temperature of about 350 to 470°C for about 1 to 36 hours, preferably in the temperature range of 400 to 460°C, and preferably in the time range of 2 to 15 hours. In this embodiment, Na ions replace part of the Li ions in the matrix glass or glass-ceramic, thereby forming a surface compression layer and exhibiting high mechanical properties. In some embodiments, the matrix glass or glass-ceramic can be ion exchanged by immersing in a mixed salt bath of molten K salt and Na salt at a temperature of about 360 to 450°C for 1 to 36 hours, preferably in the time range of 2 to 24 hours.
[0169] The glass-ceramics with spinel crystal phases disclosed in the present invention have high-efficiency low-temperature ion exchange performance. In some embodiments, at a lower ion exchange temperature and a shorter exchange time, the exchange layer depth of Na ions can reach more than 75 μm. After ion exchange, the hardness of the glass-ceramics product with spinel crystal phase is significantly improved. The main reason is that the ion exchange forms a higher compressive stress on the surface of the glass-ceramics product with spinel crystal phase through the "crowding effect", which increases the deformation resistance of the glass-ceramics product with spinel crystal phase and improves the hardness. In some embodiments, after chemical strengthening of the glass-ceramics with spinel crystal phases of the present invention, the Vickers hardness of the obtained glass-ceramics product can reach 650 kgf / mm 2 above.
[0170] The various performance indicators of the glass-ceramics having a spinel crystal phase and / or the glass-ceramics products having a spinel crystal phase of the present invention are tested by the following methods:
[0171] [Haze]
[0172] A haze tester, Minolta CM3600A, was used to prepare samples with a thickness of less than 1 mm and the test was carried out according to the standard of GB2410-80.
[0173] [Grain size]
[0174] Using a SEM scanning electron microscope, the microcrystalline glass is surface treated in HF acid, gold is sprayed on the surface of the microcrystalline glass, and the surface is scanned under the SEM scanning electron microscope to determine the size of its grains.
[0175] [Light transmittance]
[0176] The light transmittances described in this article are all external transmittances, sometimes referred to as transmittance.
[0177] The sample was processed to a thickness of less than 1 mm and the opposite surfaces were polished parallel to each other, and the average light transmittance at 400 to 800 nm was measured using a Hitachi U-41000 spectrophotometer.
[0178] The sample was processed to a thickness of less than 1 mm and the opposite surfaces were polished parallel to each other, and the light transmittance at 550 nm was measured using a Hitachi U-41000 spectrophotometer.
[0179] [Depth of ion exchange layer]
[0180] The depth of the ion exchange layer was measured using a glass surface stress meter SLP-2000.
[0181] The calculation was performed under the measurement conditions that the refractive index of the sample was 1.56 and the photoelastic constant was 29 [(nm / cm) / Mpa].
[0182] [Surface stress]
[0183] The surface stress was measured using a glass surface stress meter SLP-2000.
[0184] The calculation was performed under the measurement conditions that the refractive index of the sample was 1.56 and the photoelastic constant was 29 [(nm / cm) / Mpa].
[0185] [Drop resistance]
[0186] The drop resistance test was carried out using the directional drop tester WH-2101. By loading glass products of the same specifications on 2D microcrystalline glass products (each piece weighs 20g, and 2 pieces are loaded), laying 60-80 mesh sandpaper on the base, and letting the sample fall freely from a specified height, the sample directly hits the sandpaper, and the height of the impact that can be withstood without breaking is the drop resistance. Specifically, the test is implemented from a height of 600mm, and the height is changed in sequence through 700mm, 800mm, 900mm, 1000mm and above without breaking. For the embodiments with "drop resistance", microcrystalline glass products are used as test objects. The test data recorded as 1000mm in the embodiment indicates that even if the microcrystalline glass products with load from a height of 1000mm do not break and withstand the impact, the maximum experimental height of the drop tester WH-2101 is 2000mm.
[0187] [Drop ball test height]
[0188] A sample of a microcrystalline glass product of 145mm×67mm×0.7mm is placed on a glass supporting fixture, and a 132g steel ball is dropped from a specified height, with the drop point being the center point of the sample. The maximum drop ball test height is the impact that the sample can withstand without breaking. Specifically, the drop ball test height starts at 400mm, and the ball is dropped once at each height. If the sample does not break, the test is continued by rising 100mm successively until the sample breaks. For the embodiments with a "drop ball test height", microcrystalline glass products are used as test objects. The test data recorded as 1700mm in the embodiment indicates that even if a steel ball is dropped from a height of 1700mm, the microcrystalline glass product will not break and will withstand the impact. The drop ball test height in the present invention is sometimes referred to as the drop ball height.
[0189] [Fracture toughness]
[0190] The method of directly measuring the size of the indentation crack extension was used. The sample size was 2mm×4mm×20mm. After chamfering, grinding and polishing, the sample preparation was completed. A force of 49N was applied to the sample with a Vickers hardness indenter and maintained for 30s. After the indentation was made, the fracture strength was determined by the three-point bending method.
[0191] [Four-point bending strength]
[0192] A microcomputer-controlled electronic universal testing machine CMT6502 is used, and the sample specification is less than 1 mm thick (preferably 0.7 mm thick), and the test is performed according to the standard of "ASTM C 158-2002". In the present invention, the four-point bending strength is sometimes referred to as bending strength.
[0193] [Vickers hardness]
[0194] The load (N) when a diamond quadrangular pyramid indenter with an angle of 136° between the opposite faces is pressed into a pyramid-shaped depression on the test surface is divided by the surface area (mm2) calculated by the length of the depression. 2 ) value. The test load was 100 (N) and the holding time was 15 (seconds). In the present invention, Vickers hardness may be simply referred to as hardness.
[0195] [Compression strength]
[0196] Using a microcomputer-controlled electronic universal testing machine CMT6502, place a 145mm×67mm×0.7mm microcrystalline glass product sample on a glass supporting fixture. The extrusion rod adopts a mushroom head design with a diameter of ¢10mm and a downward pressure speed of 5mm / min until the sample is broken. Calibration with a fixture is required before testing, and the test point is at the center. Click the test button until the microcrystalline glass product sample is squeezed and broken, and record the pressure (N) when the sample breaks. For embodiments with "anti-extrusion strength", microcrystalline glass products are used as test objects. The test data recorded as 500N in the embodiment indicates that the maximum extrusion force that the microcrystalline glass product can withstand before breaking is 500N.
[0197] [|B|value]
[0198] Use Minolta CM-700d to test the B value. The sample specification is less than 1mm thick. Use the matching calibration long tube and short tube to perform instrument zero calibration and white plate calibration respectively. After calibration, use the long tube to perform air test again to determine the stability and calibration reliability of the instrument (B≤0.05). After the instrument is calibrated, place the product on the zero long tube for testing.
[0199] The |B| value is the absolute value of the B value.
[0200] [Young's modulus]
[0201] Young's modulus (E) is calculated using the following formula by ultrasonic testing of its longitudinal wave velocity and transverse wave velocity.
[0202]
[0203] G=V S 2 ρ
[0204] Where: E is Young's modulus, Pa;
[0205] G is the shear modulus, Pa;
[0206] V T is the shear wave velocity, m / s;
[0207] V S is the longitudinal wave velocity, m / s;
[0208] ρ is the glass density, g / cm 3 .
[0209] The glass-ceramic product having a spinel crystal phase of the present invention has the following properties:
[0210] 1) In some embodiments, the grain size of the glass-ceramic product having a spinel crystal phase is less than 60 nm, preferably less than 45 nm, and more preferably 10 to 30 nm.
[0211] 2) In some embodiments, the ion exchange layer depth of the glass-ceramic product having the spinel crystal phase is greater than 75 μm, preferably 80 to 150 μm, and more preferably 100 to 125 μm.
[0212] 3) In some embodiments, the surface stress of the glass-ceramic product having the spinel crystal phase is greater than 200 MPa, preferably 250 to 400 MPa, and more preferably 300 to 400 MPa.
[0213] 4) In some embodiments, the drop ball test height of the microcrystalline glass product having a spinel crystal phase is greater than 1000 mm, preferably greater than 1200 mm, and more preferably greater than 1500 mm.
[0214] 5) In some embodiments, the drop resistance of the microcrystalline glass product having a spinel crystal phase is greater than 1200 mm, preferably greater than 1300 mm, and more preferably greater than 1400 mm.
[0215] 6) In some embodiments, the fracture toughness of the glass-ceramic article having the spinel crystal phase is 1.0 MPa·m 1 / 2 Above, preferably 1.2 MPa·m 1 / 2 More preferably, 1.2 to 1.6 MPa·m 1 / 2 .
[0216] 7) In some embodiments, the four-point bending strength of the glass-ceramic product having a spinel crystal phase is 500 MPa or more, preferably 600 MPa or more, and more preferably 700-1000 MPa.
[0217] 8) In some embodiments, the compressive strength of the glass-ceramic product having the spinel crystal phase is greater than 400N, preferably 400-550N, and more preferably 450-550N.
[0218] 9) In some embodiments, the Vickers hardness (H v ) is 650kgf / mm 2 Above, preferably 660kgf / mm 2More preferably, 680 to 750 kgf / mm 2 .
[0219] 10) In some embodiments, the haze of the glass-ceramic product having a spinel crystal phase with a thickness of less than 1 mm is less than 0.3%, preferably less than 0.25%, and more preferably 0.05-0.2%. The thickness is preferably 0.2-1 mm, more preferably 0.3-0.9 mm, further preferably 0.5-0.8 mm, and further preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.
[0220] 11) In some embodiments, the average light transmittance of the spinel crystal phase microcrystalline glass product with a thickness of 1 mm or less at a wavelength of 400 to 800 nm is 87.0% or more, preferably 88.5% or more, and more preferably 89.5% or more. The thickness is preferably 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, further preferably 0.5 to 0.8 mm, and further preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.
[0221] 12) In some embodiments, the glass-ceramic product having a spinel crystal phase and having a thickness of 1 mm or less has a light transmittance of 87.0% or more, preferably 88.0% or more, and more preferably 89.0% or more at a wavelength of 550 nm. The thickness is preferably 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, further preferably 0.5 to 0.8 mm, and further preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.
[0222] 13) In some embodiments, for a glass-ceramic product having a spinel crystal phase and having a thickness of less than 1 mm, the average optical |B| value at 400 to 800 nm is less than 1.0, preferably less than 0.8, and more preferably 0.3 to 0.6. The thickness is preferably 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, further preferably 0.5 to 0.8 mm, and further preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.
[0223] The glass-ceramics having the spinel crystal phase of the present invention has the following properties:
[0224] 1) In some embodiments, the grain size of the glass-ceramics having the spinel crystal phase is less than 60 nm, preferably less than 45 nm, and more preferably 10 to 30 nm.
[0225] 2) In some embodiments, the haze of the glass-ceramics having a spinel crystal phase with a thickness of less than 1 mm is less than 0.3%, preferably less than 0.25%, and more preferably 0.05-0.2%. The thickness is preferably 0.2-1 mm, more preferably 0.3-0.9 mm, further preferably 0.5-0.8 mm, and further preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.
[0226] 3) In some embodiments, the average light transmittance of the spinel crystal phase glass-ceramics with a thickness of 1 mm or less at a wavelength of 400 to 800 nm is 87.0% or more, preferably 88.5% or more, and more preferably 89.5% or more. The thickness is preferably 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, further preferably 0.5 to 0.8 mm, and further preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.
[0227] 4) In some embodiments, the glass-ceramics having a spinel crystal phase with a thickness of 1 mm or less has a light transmittance of 87.0% or more, preferably 88.0% or more, and more preferably 89.0% or more at a wavelength of 550 nm. The thickness is preferably 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, further preferably 0.5 to 0.8 mm, and further preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.
[0228] 5) In some embodiments, the average optical |B| value of the spinel crystal phase with a thickness of less than 1 mm at 400-800 nm is less than 1.0, preferably less than 0.8, and more preferably 0.3-0.6. The thickness is preferably 0.2-1 mm, more preferably 0.3-0.9 mm, further preferably 0.5-0.8 mm, and further preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.
[0229] 6) In some embodiments, the Young's modulus (E) of the glass-ceramics having a spinel crystal phase is 80 to 110 GPa, preferably 85 to 105 GPa, and more preferably 90 to 105 GPa.
[0230] 7) In some embodiments, the Vickers hardness (H v ) is 550kgf / mm 2 Above, preferably 580kgf / mm 2 More preferably, 600 to 650 kgf / mm 2 .
[0231] The microcrystalline glass, microcrystalline glass products, matrix glass, glass formed bodies, and microcrystalline glass formed bodies of the present invention can be widely made into glass cover plates or glass components due to the above-mentioned excellent properties; at the same time, the microcrystalline glass, microcrystalline glass products, matrix glass, glass formed bodies, and microcrystalline glass formed bodies of the present invention can be applied to electronic devices or display devices, such as mobile phones, watches, computers, touch screens, etc., for manufacturing protective glass for mobile phones, smart phones, tablet computers, laptops, PDAs, televisions, personal computers, MTA machines, or industrial displays, or for manufacturing touch screens, protective windows, car windows, train windows, aviation machinery windows, touch screen protective glass, or for manufacturing hard disk substrates or solar cell substrates, or for manufacturing white household appliances, such as for manufacturing refrigerator parts or kitchen utensils.
[0232] Example
[0233] In order to further clearly illustrate and describe the technical solution of the present invention, the following non-limiting examples are provided. The present invention embodiments have been tried to ensure the accuracy of the values (such as quantity, temperature, etc.), but some errors and deviations must be taken into account. The composition itself is given in weight % based on the oxide and has been standardized to 100%.
[0234] <Glass-ceramic Example with Spinel Crystal Phase>
[0235] This embodiment adopts the above-mentioned method for manufacturing microcrystalline glass with a spinel crystal phase to obtain microcrystalline glass with a spinel crystal phase having the composition shown in Tables 1 to 4. In addition, the characteristics of each microcrystalline glass are measured by the test method described in the present invention, and the measurement results are shown in Tables 1 to 4. In the following embodiments, the thickness of the test sample for haze, average light transmittance at a wavelength of 400 to 800 nm, light transmittance at a wavelength of 550 nm, and average light |B| value at 400 to 800 nm is 0.7 mm.
[0236] Table 1.
[0237]
[0238] Table 2.
[0239]
[0240]
[0241] Table 3.
[0242]
[0243]
[0244] Table 4.
[0245]
[0246]
[0247] <Example of glass-ceramic product having spinel crystal phase>
[0248] This embodiment adopts the manufacturing method of the microcrystalline glass product with spinel crystal phase to obtain the microcrystalline glass product with spinel crystal phase having the composition shown in Table 5 to Table 8. In addition, the characteristics of each microcrystalline glass product with spinel crystal phase are measured by the test method described in the present invention, and the measurement results are shown in Table 5 to Table 8. In the following embodiments, the thickness of the test sample for haze, average light transmittance at wavelengths of 400 to 800 nm, light transmittance at wavelengths of 550 nm, and average light |B| value at 400 to 800 nm is 0.7 mm.
[0249] Table 5.
[0250]
[0251]
[0252] Table 6.
[0253]
[0254]
[0255] Table 7.
[0256]
[0257]
[0258] Table 8.
[0259]
[0260]
Claims
1. A glass-ceramic product having a spinel crystal phase, characterized in that: Its components, expressed in weight percentage, contain: SiO2: 41-55%; Al2O3+ZnO: 26-45%; Li2O: 0.1-6%; MgO: 0.1~6%; TiO2: 0.5~7%, of which Li2O / TiO2 is 0.2~4.
5.
2. The glass-ceramic product having a spinel crystal phase according to claim 1, characterized in that: Its components, expressed in weight percentage, also contain: P2O5+ZrO2: 0-8%; and / or Na2O: 0-6%; and / or B2O3: 0-4%; and / or K2O: 0-3%; and / or CaO+BaO+SrO: 0-5%; and / or Y2O3: 0-6%; and / or clarifier: 0-2%.
3. A glass-ceramic product having a spinel crystal phase, characterized in that: Its components include SiO2, Al2O3, Li2O, ZnO and TiO2. The light transmittance of the microcrystalline glass product with a thickness of less than 1 mm at a wavelength of 550 nm is more than 87.0%.
4. A glass-ceramic product having a spinel crystal phase, characterized in that: The drop ball test height of the microcrystalline glass product is above 1000 mm.
5. The glass-ceramic product having a spinel crystal phase according to claim 3 or 4, characterized in that: Its components, expressed in weight percentage, contain: SiO2: 41-55%; and / or Al2O3+ZnO: 26-45%; and / or Li2O: 0.1-6%; and / or MgO: 0.1-6%; and / or TiO2: 0.5-7%; and / or P2O5+ZrO2: 0-8%; and / or Na2O: 0-6%; and / or B2O3: 0-4%; and / or K2O: 0-3%; and / or CaO+BaO+SrO: 0-5%; and / or Y2O3: 0-6%; and / or clarifier: 0-2%.
6. The glass-ceramic product having a spinel crystal phase according to any one of claims 1 to 5, characterized in that: Its components are expressed in weight percentage, wherein: Li2O / TiO2 is 0.2-4.5, preferably Li2O / TiO2 is 0.5-3.5, more preferably Li2O / TiO2 is 0.7-2.5, and further preferably Li2O / TiO2 is 0.75-1.5; and / or Al2O3 / ZnO is 1.0-3.0, preferably Al2O3 / ZnO is 1.2-2.8, more preferably Al2O3 / ZnO is 1.25-2.5, and further preferably Al2O3 / ZnO is 1.5-2.3; and / or SiO2 / Al2O3 is 1.5-3.2, preferably SiO2 / Al2O3 is 1.7-3.0, and more preferably SiO2 / Al2O3 is 1.8-2.8 , further preferably SiO2 / Al2O3 is 2.0-2.5; and / or (TiO2+ZnO) / Al2O3 is 0.4-1.5, preferably (TiO2+ZnO) / Al2O3 is 0.5-1.2, more preferably (TiO2+ZnO) / Al2O3 is 0.6-1.0, further preferably (TiO2+ZnO) / Al2O3 is 0.6-0.9; and / or (Li2O+MgO) / TiO2 is 0.3-8.0, preferably (Li2O+MgO) / TiO2 is 0.5-5.0, more preferably (Li2O+MgO) / TiO2 is 1.0-3.0, further preferably (Li2O+MgO) / TiO2 is 1.2-2.5; and / or Al2O3 / (MgO+TiO2) is 1.3 to 10.0, preferably Al2O3 / (MgO+TiO2) is 1.5 to 8.0, more preferably Al2O3 / (MgO+TiO2) is 2.5 to 6.5, and further preferably Al2O3 / (MgO+TiO2) is 3.0 to 5.5; and / or (Al2O3+Li2O) / P2O5 is 5.0 to 45.0, preferably (Al2O3+Li2O) / P2O5 is 7.0 to 35.0, more preferably (Al2O3+Li2O) / P2O5 is 8.0 to 30.0, and further preferably (Al2O3+Li2O) / P2O5 is 10.0 to 25.0; and / or P2O5 / ZrO2 is 0.1~5.0, preferably P2O5 / ZrO2 is 0.2~3.0, more preferably P2O5 / ZrO2 is 0.5~2.0, and further preferably P2O5 / ZrO2 is 0.6~1.5; and / or (SiO2+Na2O) / ZnO is 2.2~6.2, preferably (SiO2+Na2O) / ZnO is 2.5~6.0, more preferably (SiO2+Na2O) / ZnO is 2.8~5.5, and further preferably (SiO2+Na2O) / ZnO is 3.0~5.0; and / or (Na2O+K2O) / ZnO is 0.8 or less, preferably (Na2O+K2O) / ZnO is 0.6 or less, and further preferably (Na2O+K2O) / ZnO is 0.4 or less, and more preferably (Na2O+K2O) / ZnO is 0.2 or less.
7. The glass-ceramic product having a spinel crystal phase according to any one of claims 1 to 5, characterized in that: The components thereof, expressed by weight percentage, contain: SiO2: 45-53%, preferably SiO2: 48-52%; and / or Al2O3+ZnO: 30-42%, preferably Al2O3+ZnO: 32-42%, more preferably Al2O3+ZnO: 35-40%; and / or Li2O: 1-5%, preferably Li2O: 2-4%; and / or MgO: 1-5%, preferably MgO: 2-4%; and / or TiO2: 1-6%, preferably TiO2: 2-5%; and / or P2O5+ZrO2: 0 .1~7%, preferably P2O5+ZrO2: 0.5~5%; and / or Na2O: 0~4%, preferably Na2O: 0~2%; and / or B2O3: 0~2%, preferably B2O3: 0~1%; and / or K2O: 0~2%, preferably K2O: 0~1%; and / or CaO+BaO+SrO: 0~4%, preferably CaO+BaO+SrO: 0~2%; and / or Y2O3: 0~4%, preferably Y2O3: 0~2%; and / or clarifier: 0~1%, preferably clarifier: 0~0.5%.
8. The glass-ceramic product having a spinel crystal phase according to any one of claims 1 to 5, characterized in that: Its components, expressed in weight percentage, contain: Al2O3: 15-30%, preferably Al2O3: 18-25%, more preferably Al2O3: 20-23%; and / or ZnO: 9-20%, preferably ZnO: 11-18%, more preferably ZnO: 12-16%; and / or P2O5: 0-5%, preferably P2O5: 0.5-4%, more preferably P2O5: 1-3%; and / or ZrO2: 0-5%, preferably ZrO2: 0.5-4%, more preferably ZrO2: 1-3%.
9. The glass-ceramic product having a spinel crystal phase according to any one of claims 1 to 5, characterized in that: The weight percentage of the spinel crystal phase in the microcrystalline glass product is 20-60%, preferably the weight percentage of the spinel crystal phase in the microcrystalline glass product is 25-50%, more preferably the weight percentage of the spinel crystal phase in the microcrystalline glass product is 25-45%, and further preferably the weight percentage of the spinel crystal phase in the microcrystalline glass product is 30-45%.
10. The glass-ceramic product having a spinel crystal phase according to any one of claims 1 to 5, characterized in that: The microcrystalline glass product with a spinel crystal phase contains a quartz crystal phase. Preferably, the weight percentage of the quartz crystal phase in the microcrystalline glass product is less than 20%, more preferably, the weight percentage of the quartz crystal phase in the microcrystalline glass product is less than 10%, further preferably, the weight percentage of the quartz crystal phase in the microcrystalline glass product is less than 5%, and further preferably, the microcrystalline glass product with a spinel crystal phase does not contain a quartz crystal phase.
11. The glass-ceramic product having a spinel crystal phase according to any one of claims 1 to 5, characterized in that: Its components, expressed in weight percentage, contain: La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-5%, preferably La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-2%, more preferably La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-1%, and further preferably contain no La2O3, and / or no Gd2O3, and / or no Yb2O3, and / or no Nb2O5, and / or no WO3, and / or no Bi2O3, and / or no Ta2O5, and / or no TeO2.
12. The glass-ceramic product having a spinel crystal phase according to any one of claims 1 to 5, characterized in that: The crystal size of the microcrystalline glass product is 60 nm or less, preferably 45 nm or less, more preferably 10-30 nm; and / or the depth of the ion exchange layer is 75 μm or more, preferably 80-150 μm, more preferably 100-125 μm; and / or the surface stress is 200 MPa or more, preferably 250-400 MPa, more preferably 300-400 MPa; and / or the height of the drop ball test is 1000 mm or more, preferably 1200 mm or more, more preferably 1500 mm or more; and / or the drop resistance is 1200 mm or more, preferably 1300 mm or more, more preferably 1400 mm or more; and / or the fracture toughness is 1.0 MPa·m 1 / 2 Above, preferably 1.2 MPa·m 1 / 2 More preferably, 1.2 to 1.6 MPa·m 1 / 2 ; and / or a four-point bending strength of 500 MPa or more, preferably 600 MPa or more, more preferably 700-1000 MPa; and / or an extrusion strength of 400 N or more, preferably 400-550 N, more preferably 450-550 N; and / or a Vickers hardness of 650 kgf / mm 2 Above, preferably 660kgf / mm 2 More preferably, 680 to 750 kgf / mm 2 .
13. The glass-ceramic product having a spinel crystal phase according to any one of claims 1 to 5, characterized in that: The haze of microcrystalline glass products with a thickness of less than 1 mm is less than 0.3%, preferably less than 0.25%, and more preferably 0.05-0.2%; and / or the average light transmittance at a wavelength of 400-800 nm is greater than 87.0%, preferably greater than 88.5%, and more preferably greater than 89.5%; and / or the light transmittance at a wavelength of 550 nm is greater than 87.0%, preferably greater than 88.0%, and more preferably greater than 89.0%; and / or the average light |B| value at 400-800 nm is less than 1.0, preferably less than 0.8, and more preferably 0.3-0.
6.
14. The glass-ceramic product having a spinel crystal phase according to claim 13, characterized in that: The thickness of the microcrystalline glass product is 0.2 to 1 mm, preferably 0.3 to 0.9 mm, more preferably 0.5 to 0.8 mm, and further preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm or 0.75 mm.
15. The glass-ceramic product having a spinel crystal phase according to any one of claims 1 to 5, characterized in that: Its components, expressed in weight percentage, include: NiO: 0-4%; and / or Ni2O3: 0-4%; and / or CoO: 0-2%; and / or Co2O3: 0-2%; and / or Fe2O3: 0-7%; and / or MnO2: 0-4%; and / or Er2O3: 0-8%; and / or Nd2O3: 0-8%; and / or Cu2O: 0-4%; and / or Pr2O3: 0-8%; and / or CeO2: 0-4%.
16. Glass-ceramics having a spinel crystal phase, characterized in that: Its components, expressed in weight percentage, contain: SiO2: 41-55%; Al2O3+ZnO: 26-45%; Li2O: 0.1-6%; MgO: 0.1~6%; TiO2: 0.5~7%, of which Li2O / TiO2 is 0.2~4.
5.
17. The glass-ceramic having a spinel crystal phase according to claim 16, characterized in that: Its components, expressed in weight percentage, also contain: P2O5+ZrO2: 0-8%; and / or Na2O: 0-6%; and / or B2O3: 0-4%; and / or K2O: 0-3%; and / or CaO+BaO+SrO: 0-5%; and / or Y2O3: 0-6%; and / or clarifier: 0-2%.
18. Glass-ceramics having a spinel crystal phase, characterized in that: Its components include SiO2, Al2O3, Li2O, ZnO and TiO2. The light transmittance of the microcrystalline glass with a thickness of less than 1 mm at a wavelength of 550 nm is more than 87.0%.
19. Glass-ceramics having a spinel crystal phase, characterized in that: The crystal grain size of the microcrystalline glass is less than 60 nm.
20. The glass-ceramics having a spinel crystal phase according to claim 18 or 19, characterized in that: Its components, expressed in weight percentage, contain: SiO2: 41-55%; and / or Al2O3+ZnO: 26-45%; and / or Li2O: 0.1-6%; and / or MgO: 0.1-6%; and / or TiO2: 0.5-7%; and / or P2O5+ZrO2: 0-8%; and / or Na2O: 0-6%; and / or B2O3: 0-4%; and / or K2O: 0-3%; and / or CaO+BaO+SrO: 0-5%; and / or Y2O3: 0-6%; and / or clarifier: 0-2%.
21. The glass-ceramics having a spinel crystal phase according to any one of claims 16 to 20, characterized in that: Its components are expressed in weight percentage, wherein: Li2O / TiO2 is 0.2-4.5, preferably Li2O / TiO2 is 0.5-3.5, more preferably Li2O / TiO2 is 0.7-2.5, and further preferably Li2O / TiO2 is 0.75-1.5; and / or Al2O3 / ZnO is 1.0-3.0, preferably Al2O3 / ZnO is 1.2-2.8, more preferably Al2O3 / ZnO is 1.25-2.5, and further preferably Al2O3 / ZnO is 1.5-2.3; and / or SiO2 / Al2O3 is 1.5-3.2, preferably SiO2 / Al2O3 is 1.7-3.0, and more preferably SiO2 / Al2O3 is 1.8-2.8 , further preferably SiO2 / Al2O3 is 2.0-2.5; and / or (TiO2+ZnO) / Al2O3 is 0.4-1.5, preferably (TiO2+ZnO) / Al2O3 is 0.5-1.2, more preferably (TiO2+ZnO) / Al2O3 is 0.6-1.0, further preferably (TiO2+ZnO) / Al2O3 is 0.6-0.9; and / or (Li2O+MgO) / TiO2 is 0.3-8.0, preferably (Li2O+MgO) / TiO2 is 0.5-5.0, more preferably (Li2O+MgO) / TiO2 is 1.0-3.0, further preferably (Li2O+MgO) / TiO2 is 1.2-2.5; and / or Al2O3 / (MgO+TiO2) is 1.3 to 10.0, preferably Al2O3 / (MgO+TiO2) is 1.5 to 8.0, more preferably Al2O3 / (MgO+TiO2) is 2.5 to 6.5, and further preferably Al2O3 / (MgO+TiO2) is 3.0 to 5.5; and / or (Al2O3+Li2O) / P2O5 is 5.0 to 45.0, preferably (Al2O3+Li2O) / P2O5 is 7.0 to 35.0, more preferably (Al2O3+Li2O) / P2O5 is 8.0 to 30.0, and further preferably (Al2O3+Li2O) / P2O5 is 10.0 to 25.0; and / or P2O5 / ZrO2 is 0.1~5.0, preferably P2O5 / ZrO2 is 0.2~3.0, more preferably P2O5 / ZrO2 is 0.5~2.0, and further preferably P2O5 / ZrO2 is 0.6~1.5; and / or (SiO2+Na2O) / ZnO is 2.2~6.2, preferably (SiO2+Na2O) / ZnO is 2.5~6.0, more preferably (SiO2+Na2O) / ZnO is 2.8~5.5, and further preferably (SiO2+Na2O) / ZnO is 3.0~5.0; and / or (Na2O+K2O) / ZnO is 0.8 or less, preferably (Na2O+K2O) / ZnO is 0.6 or less, and further preferably (Na2O+K2O) / ZnO is 0.4 or less, and more preferably (Na2O+K2O) / ZnO is 0.2 or less.
22. The glass-ceramics having a spinel crystal phase according to any one of claims 16 to 20, characterized in that: The components thereof, expressed by weight percentage, contain: SiO2: 45-53%, preferably SiO2: 48-52%; and / or Al2O3+ZnO: 30-42%, preferably Al2O3+ZnO: 32-42%, more preferably Al2O3+ZnO: 35-40%; and / or Li2O: 1-5%, preferably Li2O: 2-4%; and / or MgO: 1-5%, preferably MgO: 2-4%; and / or TiO2: 1-6%, preferably TiO2: 2-5%; and / or P2O5+ZrO2: 0 .1~7%, preferably P2O5+ZrO2: 0.5~5%; and / or Na2O: 0~4%, preferably Na2O: 0~2%; and / or B2O3: 0~2%, preferably B2O3: 0~1%; and / or K2O: 0~2%, preferably K2O: 0~1%; and / or CaO+BaO+SrO: 0~4%, preferably CaO+BaO+SrO: 0~2%; and / or Y2O3: 0~4%, preferably Y2O3: 0~2%; and / or clarifier: 0~1%, preferably clarifier: 0~0.5%.
23. The glass-ceramics having a spinel crystal phase according to any one of claims 16 to 20, characterized in that: Its components, expressed in weight percentage, contain: Al2O3: 15-30%, preferably Al2O3: 18-25%, more preferably Al2O3: 20-23%; and / or ZnO: 9-20%, preferably ZnO: 11-18%, more preferably ZnO: 12-16%; and / or P2O5: 0-5%, preferably P2O5: 0.5-4%, more preferably P2O5: 1-3%; and / or ZrO2: 0-5%, preferably ZrO2: 0.5-4%, more preferably ZrO2: 1-3%.
24. The glass-ceramics having a spinel crystal phase according to any one of claims 16 to 20, characterized in that: The weight percentage of the spinel crystal phase in the microcrystalline glass is 20-60%, preferably the weight percentage of the spinel crystal phase in the microcrystalline glass is 25-50%, more preferably the weight percentage of the spinel crystal phase in the microcrystalline glass is 25-45%, and further preferably the weight percentage of the spinel crystal phase in the microcrystalline glass is 30-45%.
25. The glass-ceramics having a spinel crystal phase according to any one of claims 16 to 20, characterized in that: The microcrystalline glass with a spinel crystal phase contains a quartz crystal phase. Preferably, the weight percentage of the quartz crystal phase in the microcrystalline glass is less than 20%, more preferably, the weight percentage of the quartz crystal phase in the microcrystalline glass is less than 10%, further preferably, the weight percentage of the quartz crystal phase in the microcrystalline glass is less than 5%, and further preferably, the microcrystalline glass with a spinel crystal phase does not contain a quartz crystal phase.
26. The glass-ceramics having a spinel crystal phase according to any one of claims 16 to 20, characterized in that: Its components, expressed in weight percentage, contain: La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-5%, preferably La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-2%, more preferably La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-1%, and further preferably contain no La2O3, and / or no Gd2O3, and / or no Yb2O3, and / or no Nb2O5, and / or no WO3, and / or no Bi2O3, and / or no Ta2O5, and / or no TeO2.
27. The glass-ceramics having a spinel crystal phase according to any one of claims 16 to 20, characterized in that: The crystal size of the microcrystalline glass is less than 60 nm, preferably less than 45 nm, more preferably 10 to 30 nm; and / or the Young's modulus is 80 to 110 GPa, preferably 85 to 105 GPa, more preferably 90 to 105 GPa; and / or the Vickers hardness is 550 kgf / mm 2 Above, preferably 580kgf / mm 2 More preferably, 600 to 650 kgf / mm 2 .
28. The glass-ceramics having a spinel crystal phase according to any one of claims 16 to 20, characterized in that: The haze of microcrystalline glass with a thickness of less than 1 mm is less than 0.3%, preferably less than 0.25%, more preferably 0.05-0.2%; and / or the average light transmittance at a wavelength of 400-800 nm is greater than 87.0%, preferably greater than 88.5%, more preferably greater than 89.5%; and / or the light transmittance at a wavelength of 550 nm is greater than 87.0%, preferably greater than 88.0%, more preferably greater than 89.0%; and / or the average light |B| value at 400-800 nm is less than 1.0, preferably less than 0.8, more preferably 0.3-0.
6.
29. The glass-ceramic having a spinel crystal phase according to claim 28, characterized in that: The thickness of the glass-ceramics is 0.2 to 1 mm, preferably 0.3 to 0.9 mm, more preferably 0.5 to 0.8 mm, and further preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm or 0.75 mm.
30. The glass-ceramics having a spinel crystal phase according to any one of claims 16 to 20, characterized in that: Its components, expressed in weight percentage, include: NiO: 0-4%; and / or Ni2O3: 0-4%; and / or CoO: 0-2%; and / or Co2O3: 0-2%; and / or Fe2O3: 0-7%; and / or MnO2: 0-4%; and / or Er2O3: 0-8%; and / or Nd2O3: 0-8%; and / or Cu2O: 0-4%; and / or Pr2O3: 0-8%; and / or CeO2: 0-4%.
31. A glass cover plate, characterized in that: A glass-ceramic product having a spinel crystal phase according to any one of claims 1 to 15, and / or a glass-ceramic product having a spinel crystal phase according to any one of claims 16 to 30.
32. A glass component, characterized in that: A glass-ceramic product having a spinel crystal phase according to any one of claims 1 to 15, and / or a glass-ceramic product having a spinel crystal phase according to any one of claims 16 to 30.
33. An electronic device, characterized in that A glass-ceramic product having a spinel crystal phase as described in any one of claims 1 to 15, and / or a glass-ceramic product having a spinel crystal phase as described in any one of claims 16 to 30, and / or a glass cover plate as described in claim 31, and / or a glass component as described in claim 32.
34. A display device, characterized in that A glass-ceramic product having a spinel crystal phase as described in any one of claims 1 to 15, and / or a glass-ceramic product having a spinel crystal phase as described in any one of claims 16 to 30, and / or a glass cover plate as described in claim 31, and / or a glass component as described in claim 32.
35. The method for manufacturing a glass-ceramic product having a spinel crystal phase according to any one of claims 1 to 15, characterized in that: The method comprises the following steps: forming a matrix glass, subjecting the matrix glass to a crystallization process to form a microcrystalline glass having a spinel crystal phase, and then subjecting the microcrystalline glass having a spinel crystal phase to a chemical strengthening process to form a microcrystalline glass product having a spinel crystal phase.
36. The method for manufacturing a glass-ceramic product having a spinel crystal phase according to claim 35, characterized in that: The forming of the matrix glass comprises the following steps: The raw materials are mixed uniformly according to the component ratio, then put into a crucible, and melted in an electric furnace or a gas furnace at a temperature range of 1350 to 1550° C. for 5 to 24 hours, preferably at a melting temperature of 1450 to 1550° C., and then clarified, homogenized, formed, and annealed to obtain a matrix glass, wherein the clarification temperature is greater than 1550° C. but less than or equal to 1650° C., and the annealing temperature is 450 to 600° C.
37. The method for manufacturing a glass-ceramic product having a spinel crystal phase according to claim 35, characterized in that: The crystallization process includes the following steps: heating to a prescribed crystallization treatment temperature, maintaining the temperature for a certain period of time after reaching the crystallization treatment temperature, and then cooling down. The crystallization treatment temperature is 600-800°C, preferably 650-750°C, and the holding time at the crystallization treatment temperature is 1-10 hours, preferably 3-6 hours.
38. The method for manufacturing a glass-ceramic product having a spinel crystal phase according to claim 35, characterized in that: The crystallization process includes the following steps: performing a nucleation process at a first temperature, and then performing a crystal growth process at a second temperature, wherein the first temperature is 600-700°C, the second temperature is greater than 700°C but less than or equal to 800°C, the holding time at the first temperature is 1-6 hours, and the holding time at the second temperature is 2-5 hours.
39. The method for manufacturing a glass-ceramic product having a spinel crystal phase according to claim 35, characterized in that: The chemical strengthening process includes: immersing the microcrystalline glass having a spinel crystal phase in a salt bath of molten Na salt at 350-470°C for 1-36 hours, preferably in the temperature range of 400-460°C, and preferably in the time range of 2-15 hours; and / or immersing the microcrystalline glass having a spinel crystal phase in a mixed salt bath of molten K salt and Na salt at 360-450°C for 1-36 hours, preferably in the time range of 2-24 hours.
40. The method for producing glass-ceramics having a spinel crystal phase according to any one of claims 16 to 30, characterized in that: The method comprises the following steps: forming a matrix glass, and then forming a microcrystalline glass having a spinel crystal phase through a crystallization process.
41. The method for manufacturing glass-ceramics having a spinel crystal phase according to claim 40, characterized in that: The forming of the matrix glass comprises the following steps: The raw materials are mixed uniformly according to the component ratio, then put into a crucible, and melted in an electric furnace or a gas furnace at a temperature range of 1350 to 1550° C. for 5 to 24 hours, preferably at a melting temperature of 1450 to 1550° C., and then clarified, homogenized, formed, and annealed to obtain a matrix glass, wherein the clarification temperature is greater than 1550° C. but less than or equal to 1650° C., and the annealing temperature is 450 to 600° C.
42. The method for manufacturing glass-ceramics having a spinel crystal phase according to claim 40, characterized in that: The crystallization process includes the following steps: heating to a prescribed crystallization treatment temperature, maintaining the temperature for a certain period of time after reaching the crystallization treatment temperature, and then cooling down. The crystallization treatment temperature is 600-800°C, preferably 650-750°C, and the holding time at the crystallization treatment temperature is 1-10 hours, preferably 3-6 hours.
43. The method for manufacturing a glass-ceramic product having a spinel crystal phase according to claim 40, characterized in that: The crystallization process includes the following steps: performing a nucleation process at a first temperature, and then performing a crystal growth process at a second temperature, wherein the first temperature is 600-700°C, the second temperature is greater than 700°C but less than or equal to 800°C, the holding time at the first temperature is 1-6 hours, and the holding time at the second temperature is 2-5 hours.
Citation Information
Patent Citations
Crystallized glass substrate for information recording medium and method of producing the same
CN101905952A
Glass ceramic, glass ceramic product and manufacturing method thereof
CN114907014A
Tempered glass, microcrystalline glass and preparation method and application thereof
CN115286251A